Toner binder manufacturing method
A toner binder is produced by polymerizing a monomer composition with a crystalline vinyl resin and mixing it with an amorphous polyester, enhancing compatibility and performance in terms of low-temperature fixing, hot offset resistance, and image strength.
Patent Information
- Application Number
- JP2021154733
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-13
- Filing Date
- 2021-09-22
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2041-09-22
AI Technical Summary
Existing toner binders fail to balance low-temperature fixing properties, hot offset resistance, fixing width, wrapping properties, and image strength, particularly when using crystalline vinyl resins with long-chain alkyl acrylate, leading to issues like high-temperature offset and poor miscibility.
A method involving the polymerization of a monomer composition containing a monomer with a vinyl group in the presence of a crystalline vinyl resin, followed by mixing with an amorphous polyester resin, to create a toner binder that achieves improved compatibility and performance.
The resulting toner binder maintains low-temperature fixing properties, exhibits excellent hot offset resistance, and enhances image strength and wrapping properties, addressing the limitations of previous formulations.
Smart Images

Figure 0007605718000001 
Figure 0007605718000002 
Figure 0007605718000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for making a toner binder. [Background technology]
[0002] In recent years, with the development of electrophotographic systems, the demand for electrophotographic devices such as copying machines and laser printers has been rapidly increasing, and the demands on toners for their performance have been becoming more and more sophisticated, as have the demands on toner binders, which are the main components of toners.
[0003] Conventionally, in full-color electrophotography, a method and apparatus are known in which a latent image based on color image information is formed on a latent image carrier such as an electrophotographic photoreceptor, the latent image is developed with a toner of a corresponding color, and then the toner image is transferred onto a transfer material, and then the image forming process is repeated, and the toner image on the transfer material is heated and fixed to obtain a multicolor image. In order to pass through these processes without any problems, the toner must first maintain a stable charge amount, and then must have good fixability to paper.
[0004] Furthermore, in order to promote miniaturization, speedup, and image quality improvement of electrophotographic apparatuses, as well as to save energy by reducing the energy consumed in the fixing process, there is a strong demand for improving the low-temperature fixability of toner. Recently, many kinds of paper are used as transfer materials, such as recycled paper with large surface irregularities and coated paper with smooth surfaces. To accommodate the surface properties of these transfer materials, a fixing device with a wide nip width, such as a soft roller or belt roller, is preferably used. However, when the nip width is widened, the contact area between the toner and the fixing roller increases, and the so-called high-temperature offset phenomenon, in which the molten toner adheres to the fixing roller, is easily generated, so hot offset resistance is required.
[0005] Known materials for toner binders that can realize the toner characteristics described above include vinyl resins (polystyrene resins, styrene-acrylic resins, etc.), polyester resins, epoxy resins, polyurethane resins, polyamide resins, etc., and recently, vinyl resins and polyester resins have been attracting particular attention because they are easy to balance between fixability and heat-resistant storage stability.
[0006] As a method for further improving the balance between fixability and heat-resistant storage stability, a toner binder has been proposed that combines a vinyl resin polymerized with a long-chain alkyl acrylate and a polyester resin having an unsaturated carboxylic acid as a constituent component (see, for example, Patent Document 1). According to the technology described in Patent Document 1, it is possible to achieve both improved low-temperature fixability by the vinyl resin and hot offset resistance by the polyester resin. In the manufacturing process of the toner binder described in Patent Document 1, the vinyl resin and the polyester resin are mixed by a method such as powder mixing, melt mixing, or solvent mixing, but the toner binder obtained due to the poor mixability has a large dispersion diameter, and the toner performance such as fixability and image strength is insufficient.
[0007] The technology described in Patent Document 2 is known as a solution to these problems. According to the technology described in Patent Document 2, a toner having a sea-island structure is obtained by using a crystalline vinyl resin and an amorphous vinyl resin in combination, which makes it possible to realize a toner that is resistant to external forces such as rubbing and scratching while maintaining fixability. However, if a large amount (e.g., 93% by weight or more) of long-chain alkyl acrylate is used as a constituent of the crystalline vinyl resin, the miscibility and durability are insufficient, and further, since the long-chain alkyl acrylate has low polarity, it is easily compatible with wax, and the wax is less likely to bleed onto the toner surface after fixing. As a result, the hot offset resistance is reduced, and it is difficult to reduce the resistance between the paper and the transport roller, which causes the paper to wrap around the roller.
[0008] As described above, there has not been a toner binder that satisfies all of the performance requirements of low-temperature fixing property, hot offset resistance, fixing width (difference between low-temperature fixing temperature and hot offset resistance temperature), winding property, heat-resistant storage stability, and image strength. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] International Publication No. 2019 / 073731 [Patent Document 2] JP2014-142632A Summary of the Invention [Problem to be solved by the invention]
[0010] An object of the present invention is to provide a toner binder for use in a toner that is excellent in hot offset resistance, fixing width, winding property and image strength while maintaining low-temperature fixing property and heat-resistant storage stability. [Means for solving the problem]
[0011] As a solution to the above problems, the inventors have intensively studied and found that the above problems can be solved by a toner binder obtained by a production method including step 1 of polymerizing a monomer composition (B0) containing a monomer (b1) having a vinyl group in the presence of a crystalline vinyl resin (C) and step 2 of mixing the composition (X) obtained in step 1 with an amorphous polyester. That is, the present invention is a production method for a toner binder including step 1 of polymerizing a monomer composition (B0) containing a monomer (b1) having a vinyl group in the presence of a crystalline vinyl resin (C) to obtain a resin composition (X) and step 2 of mixing the resin composition (X) with an amorphous polyester resin (A), in which the crystalline vinyl resin (C) is a polymer of a monomer composition (C0) containing a monomer (c1) and a monomer (c2), the monomer (c1) is a (meth)acrylate having 21 to 40 carbon atoms and a chain hydrocarbon group, and the monomer (c2) is a monomer having 6 or less carbon atoms and a vinyl group. Effect of the Invention
[0012] According to the present invention, it is possible to provide a toner binder for use in a toner that is excellent in hot offset resistance, fixing width, winding property and image strength while maintaining low-temperature fixing property and heat-resistant storage stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The method for producing a toner binder of the present invention includes step 1 of obtaining a resin composition (X) by polymerizing a monomer composition (B0) containing a monomer (b1) having a vinyl group in the presence of a crystalline vinyl resin (C), and step 2 of mixing the resin composition (X) with an amorphous polyester resin (A). The method for producing the toner binder of the present invention will be described below in detail.
[0014] [Process 1] Step 1 is a step of obtaining a resin composition (X) by polymerizing a monomer composition (B0) containing a monomer having a vinyl group in the presence of a crystalline vinyl resin (C).
[0015] In step 1, the monomer composition (B0) is polymerized in the presence of the crystalline vinyl resin (C) to obtain a resin composition (X). The resin composition (X) contains the crystalline vinyl resin (C) and a polymer of the monomer composition (B0). In the resin composition (X), the polymer of the monomer composition (B0) is dispersed more uniformly than when the crystalline vinyl resin (C) is mixed with the polymer of the monomer composition (B0) prepared separately from (C), so that the polymer of the monomer composition (B0) is more easily dispersed in the toner binder, and the compatibility between the polymer of the monomer composition (B0) and the crystalline vinyl resin (C) during toner fixing is improved. As a result, the performance (low-temperature fixing property, fixing width, charge retention rate, etc.) of the toner using the toner binder obtained by this manufacturing method can be improved. The polymer of the monomer composition (B0) is preferably an amorphous vinyl resin.
[0016] [Crystalline vinyl resin (C)] The crystalline vinyl resin (C) is a polymer of a monomer composition (C0) containing a monomer (c1) and a monomer (c2), and is a crystalline vinyl resin. The monomer (c1) is a (meth)acrylate having 21 to 40 carbon atoms and a chain-like hydrocarbon group, and the monomer (c2) is a monomer having 6 or less carbon atoms and a vinyl group. In the present invention, "(meth)acrylate" means acrylate and / or methacrylate. In the present invention, "crystalline" means that in differential scanning calorimetry (also referred to as DSC measurement) described later, the DSC curve has a peak top temperature of an endothermic peak. In the present invention, "amorphous" means that when the transition temperature of a sample is measured using a differential scanning calorimeter (DSC), there is no peak top temperature of an endothermic peak.
[0017] The method for measuring the peak top temperature of the endothermic peak of the crystalline vinyl resin (C) is described below. The measurement is performed using a differential scanning calorimeter {e.g., "DSCQ20" [manufactured by TA Instruments, Inc.]}. The crystalline vinyl resin (C) is heated for the first time from 20°C to 150°C at 10°C / min, then cooled from 150°C to 0°C at 10°C / min, and then heated for the second time from 0°C to 150°C at 10°C / min. The temperature showing the top of the endothermic peak during the second heating process is taken as the peak top temperature of the endothermic peak of the crystalline vinyl resin (C).
[0018] The monomer (c1) is a (meth)acrylate having a chain hydrocarbon group and carbon number of 21 to 40. The monomer (c1) may be used alone or in combination of two or more kinds.
[0019] Examples of the monomer (c1) include (meth)acrylates having a linear alkyl group (alkyl group having 18 to 36 carbon atoms) [octadecyl (meth)acrylate (stearyl (meth)acrylate), nonadecyl (meth)acrylate, eicosyl (meth)acrylate, heneicosanyl (meth)acrylate, behenyl (meth)acrylate, lignoceryl (meth)acrylate, ceryl (meth)acrylate, montanyl (meth)acrylate, triacontyl (meth)acrylate (myrisyl (meth)acrylate), dodriacotyl (meth)acrylate, and the like] and (meth)acrylates having a branched alkyl group (alkyl group having 18 to 36 carbon atoms) [2-decyltetradecyl (meth)acrylate, and the like].
[0020] Among these, from the viewpoint of improving the low-temperature fixing property and heat-resistant storage stability of the toner, preferred are (meth)acrylates having a linear alkyl group (alkyl group having 18 to 36 carbon atoms), more preferred are (meth)acrylates having a linear alkyl group (alkyl group having 18 to 30 carbon atoms), even more preferred are octadecyl (meth)acrylate, arachidyl (meth)acrylate, behenyl (meth)acrylate, lignoceryl (meth)acrylate, ceryl (meth)acrylate, and triacontyl (meth)acrylate, and particularly preferred are octadecyl acrylate, arachidyl acrylate, behenyl acrylate, and lignoceryl acrylate.
[0021] The monomer (c2) is a vinyl group-containing monomer having a carbon number of not more than 6. The monomer (c2) may be used alone or in combination of two or more kinds. Examples of the monomer (c2) include (meth)acrylic monomers having 6 or less carbon atoms [(meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, 2-hydroxypropyl acrylate, 2-hydroxyethyl (meth)acrylate, ethyl-2-(hydroxymethyl)acrylate, etc.], vinyl ester monomers having 6 or less carbon atoms [vinyl acetate, vinyl propionate, isopropenyl acetate, etc.], aliphatic hydrocarbon vinyl monomers having 6 or less carbon atoms [ethylene, propylene, butene, butadiene, isoprene, 1,5-hexadiene, etc.], and monomers having 6 or less carbon atoms and a nitrile group [(meth)acrylonitrile, etc.].
[0022] Among these, from the viewpoint of improving the hot offset resistance and image strength of the toner, preferred are (meth)acrylic monomers having 6 or less carbon atoms, vinyl ester monomers having 6 or less carbon atoms, and monomers having 6 or less carbon atoms and a nitrile group, more preferred are (meth)acrylic acid, methyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, vinyl acetate, (meth)acrylonitrile, and 2-hydroxypropyl acrylate, and even more preferred are (meth)acrylic acid, methyl (meth)acrylate, and (meth)acrylonitrile. In this specification, (meth)acrylic monomers mean acrylic monomers and / or methacrylic monomers. In this specification, (meth)acrylic acid means acrylic acid and / or methacrylic acid. In addition, in this specification, the term "(meth)acrylonitrile" means "acrylonitrile" and / or "methacrylonitrile".
[0023] The monomer composition (C0) containing the monomer (c1) and the monomer (c2) may be used in combination with a monomer (monomer (c3)) other than the monomer (c1) and the monomer (c2) as necessary. The monomer (c3) may be used alone or in combination with two or more kinds. Examples of the monomer (c3) include styrene-based monomers (c3-1), (meth)acrylic monomers (c3-2) having more than 6 carbon atoms, excluding (c1), vinyl ester monomers (c3-3) having more than 6 carbon atoms, and (meth)acrylic monomers (c3-4) other than (c1), (c2), and (c3-1) to (c3-3).
[0024] Examples of the styrene-based monomer (c3-1) include styrene, alkylstyrenes having an alkyl group with a carbon number of 1 to 3 (for example, α-methylstyrene and p-methylstyrene), etc. Among these, styrene is preferred.
[0025] Examples of the (meth)acrylic monomer (c3-2) include alkyl (meth)acrylates having an alkyl group with 4 to 17 carbon atoms [butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, etc.], hydroxyalkyl (meth)acrylates having an alkyl group with 4 to 17 carbon atoms, aminoalkyl group-containing (meth)acrylates having an alkyl group with 4 to 17 carbon atoms [dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, etc.], and esters of (meth)acrylic acid having 8 to 20 carbon atoms and polyhydric alcohols [ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, 1,6-hexanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate, etc.].
[0026] Examples of the vinyl ester monomer (c3-3) include aliphatic vinyl esters having 7 to 15 carbon atoms and aromatic vinyl esters having 9 to 15 carbon atoms (for example, methyl-4-vinylbenzoate, etc.).
[0027] Examples of (c3-4) include alkoxypolyethylene glycol (meth)acrylates (for example, methoxypolyethylene glycol acrylate, etc.).
[0028] Among these monomers (c3), from the viewpoint of improving the heat-resistant storage stability of the toner, preferred are the styrene-based monomers (c3-1) and the (meth)acrylic monomers (c3-2) having more than 6 carbon atoms, excluding (c1), more preferred are styrene, alkyl (meth)acrylates having an alkyl group with 4 to 17 carbon atoms, and esters of unsaturated carboxylic acids having 8 to 20 carbon atoms and polyhydric alcohols, and even more preferred are styrene, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and 1,6-hexanediol di(meth)acrylate.
[0029] From the viewpoint of improving the low-temperature fixing property and heat-resistant storage stability of the toner, the weight proportion of the monomer (c1) in the monomer composition (C0) is preferably 40 to 90% by weight, more preferably 45 to 90% by weight, and even more preferably 45 to 80% by weight, based on the weight of the monomer composition (C0).
[0030] From the viewpoint of improving the hot offset resistance and image strength of the toner, the weight proportion of the monomer (c2) in the monomer composition (C0) is preferably 7 to 60% by weight, more preferably 7 to 50% by weight, and even more preferably 8 to 40% by weight, based on the weight of the monomer composition (C0).
[0031] When the monomer composition (C0) contains the monomer (c3), from the viewpoint of improving the durability of the toner, the weight proportion of the monomer (c3) in the monomer composition (C0) is preferably 9 to 32 weight % based on the weight of the monomer composition (C0).
[0032] The crystalline vinyl resin (C) can be produced by polymerizing the monomer composition (C0) by a known method (e.g., radical polymerization, anionic polymerization, cationic polymerization, living radical polymerization, living anionic polymerization, living cationic polymerization, etc.). In the case of radical polymerization, for example, the resin can be synthesized by a solution polymerization method (JP Patent Publication 5-117330, etc.) in which the monomer is reacted with a radical reaction initiator (cs) in a solvent (toluene, etc.). Examples of the radical reaction initiator (cs) include the same as the radical reaction initiator (bs) described below. The toner binder obtained by the method of the present invention may contain the compound used in the polymerization of the above-mentioned crystalline vinyl resin (C) and its residue, within the range not impairing the effects of the present invention.
[0033] The amount of the radical reaction initiator (cs) used is not particularly limited, but is preferably 0.01 to 2 parts by weight based on 100 parts by weight of the monomer composition (C0).
[0034] From the viewpoint of improving the toner performance (low-temperature fixing property, heat-resistant storage stability, and image strength), the peak top temperature Tmc of the endothermic peak of the crystalline vinyl resin (C) is preferably 40 to 100° C. When Tmc is 40° C. or higher, the heat-resistant storage stability and image strength of the toner binder can be improved, and when Tmc is 100° C. or lower, the low-temperature fixing property of the toner binder can be improved. The peak top temperature of the endothermic peak of the crystalline vinyl resin (C) is more preferably from 45 to 95°C, further preferably from 50 to 90°C, and particularly preferably from 53 to 75°C.
[0035] The half-value width of the endothermic peak showing the peak top temperature of the crystalline vinyl resin (C) in the present invention is preferably 6° C. or less, from the viewpoint of improving the low-temperature fixability and heat-resistant storage stability of the toner binder. The half-width of the endothermic peak indicating the peak top temperature of the crystalline vinyl resin (C) refers to the temperature width of the peak at half the height from the baseline of the endothermic peak to the maximum height of the peak, based on a DSC curve obtained by measuring the endothermic peak temperature.
[0036] The acid value of the crystalline vinyl resin (C) in the present invention is preferably 60 mgKOH / g or less. When the acid value is 60 mgKOH / g or less, the peak top temperature Tmc of the endothermic peak increases and the moisture absorption decreases, so that the heat-resistant storage stability of the toner binder becomes good. The acid value of the crystalline vinyl resin (C) is more preferably 50 mgKOH / g or less, further preferably 40 mgKOH / g or less, and particularly preferably 0 to 30 mgKOH / g. The acid value of the crystalline vinyl resin (C) can be adjusted by the acid value of the monomer and the content of the monomer having an acid value. The acid value of (C) is measured by a method such as JIS K0070.
[0037] The weight average molecular weight of the crystalline vinyl resin (C) in the present invention, as measured by gel permeation chromatography (GPC), is preferably from 2,000 to 200,000, more preferably from 5,000 to 100,000, and even more preferably from 15,000 to 80,000, from the viewpoint of improving the low temperature fixing property, hot offset resistance, and fixing width of the toner binder.
[0038] The number average molecular weight (hereinafter sometimes abbreviated as Mn) and weight average molecular weight (hereinafter sometimes abbreviated as Mw) of the crystalline vinyl resin (C) can be measured using GPC under the following conditions. Equipment (example): HLC-8120 [Tosoh Corporation] Column (example): 2 TSK GEL GMH6 [Tosoh Corporation] Measurement temperature: 40℃ Sample solution: 0.25% by weight in THF Mobile phase: Tetrahydrofuran (no polymerization inhibitor) Solution injection volume: 100μL Detector: Refractive index detector Reference material: 12 standard polystyrenes (TSKstandard POLYSTYRENE) (molecular weight 500 1,050 2,800 5,970 9,100 18,100 37,900 96,400 190,000 355,000 1,090,000 2,890,000) For measuring the molecular weight, a sample is dissolved in THF to a concentration of 0.25% by weight, and the insoluble matter is filtered off using a PTFE filter having an aperture of 1 μm to obtain a sample solution.
[0039] [Monomer composition (B0)] The monomer composition (B0) used in step 1 contains a monomer (b1) having a vinyl group.
[0040] Examples of the monomer (b1) having a vinyl group include styrene-based monomers, (meth)acrylic-based monomers, vinyl ester monomers, aliphatic hydrocarbon-based vinyl monomers, and nitrile group-containing monomers. These monomers may be used alone or in combination of two or more.
[0041] Examples of the styrene-based monomer include styrene, alkylstyrenes having an alkyl group with a carbon number of 1 to 3 (for example, α-methylstyrene and p-methylstyrene), etc. These monomers may be used alone or in combination of two or more.
[0042] Examples of (meth)acrylic monomers include alkyl esters having an alkyl group with 1 to 16 carbon atoms [e.g., methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, etc.], hydroxyl group-containing (meth)acrylates [e.g., hydroxyethyl (meth)acrylate, etc.], amino group-containing (meth)acrylates having an alkyl group with 1 to 16 carbon atoms [e.g., dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, etc.], (meth)acrylic acid, etc.
[0043] Examples of the vinyl ester monomer include aliphatic vinyl esters (having 4 to 15 carbon atoms, such as vinyl acetate, vinyl propionate, and isopropenyl acetate).
[0044] Examples of the aliphatic hydrocarbon vinyl monomer include olefins (having 2 to 10 carbon atoms, such as ethylene, propylene, butene, isobutylene, pentene, heptene, diisobutylene, octene, dodecene, octadecene, and α-olefins other than the above), and dienes (having 4 to 10 carbon atoms, such as butadiene, isoprene, 1,4-pentadiene, 1,5-hexadiene, and 1,7-octadiene).
[0045] Examples of the nitrile group-containing monomer include acrylonitrile, methacrylonitrile, and nitrile group-containing monomers in which the methyl group of methacrylonitrile is replaced with an alkyl group having 2 to 16 carbon atoms.
[0046] Of the monomers (b1) having a vinyl group, preferred are styrene-based monomers, (meth)acrylic monomers, and nitrile group-containing monomers, and more preferred are styrene, methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, (meth)acrylic acid, acrylonitrile, and methacrylonitrile.
[0047] The monomer composition (B0) may contain, in addition to the vinyl group-containing monomer (b1), another monomer (b2) in combination, if necessary.
[0048] When the monomer composition (B0) contains styrene, the weight proportion of styrene in the monomer composition (BO) is preferably 30% by weight or more, more preferably 35 to 90% by weight, and even more preferably 35 to 80% by weight, based on the weight of the monomer composition (B0), from the viewpoint of improving the heat-resistant storage stability of the toner binder. Furthermore, the weight ratio of the (meth)acrylate having a chain hydrocarbon group and 21 to 40 carbon atoms in the monomer composition (BO) is preferably 30% by weight or less, and more preferably 10% by weight or less.
[0049] [Polymerization method] The polymerization method of the monomer composition (B0) in step 1 is not particularly limited as long as it is carried out in the presence of the crystalline vinyl resin (C), and includes known methods (for example, radical polymerization, anionic polymerization, cationic polymerization, living radical polymerization, living anionic polymerization, and living cationic polymerization). In the case of radical polymerization, it can be reacted together with a radical reaction initiator (bs), and examples of the radical reaction initiator (bs) include inorganic peroxides (bs1), organic peroxides (bs2), and azo compounds (bs3). These radical reaction initiators may be used alone or in combination of two or more.
[0050] The inorganic peroxide (bs1) is not particularly limited, but examples thereof include hydrogen peroxide, ammonium persulfate, potassium persulfate, and sodium persulfate.
[0051] The organic peroxide (bs2) is not particularly limited, but examples thereof include benzoyl peroxide, di-t-butyl peroxide, t-butylcumyl peroxide, dicumyl peroxide, α,α-bis(t-butylperoxy)diisopropylbenzene, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane, di-t-hexyl peroxide, 2,5-dimethyl-2,5-di-t-butylperoxyhexyne-3, acetyl peroxide, isobutyryl peroxide, octanyl peroxide, and decanolyl peroxide. , lauroyl peroxide, 3,3,5-trimethylhexanoyl peroxide, m-toluyl peroxide, t-butyl peroxyisobutyrate, t-butyl peroxyneodecanoate, cumyl peroxyneodecanoate, t-butyl peroxy-2-ethylhexanoate, t-butyl peroxy-3,5,5-trimethylhexanoate, t-butyl peroxylaurate, t-butyl peroxybenzoate, t-butyl peroxyisopropyl monocarbonate, and t-butyl peroxyacetate.
[0052] The azo compound (bs3) is not particularly limited, but examples thereof include 2,2'-azobis-(2,4-dimethylvaleronitrile), 2,2'-azobisisobutyronitrile, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis-4-methoxy-2,4-dimethylvaleronitrile, 2,2'-azobis(2-methylbutyronitrile), and azobisisobutyronitrile.
[0053] The amount of the radical reaction initiator (bs) used is not particularly limited, but is preferably 0.01 to 1 part by weight based on 100 parts by weight of the monomer composition (B0).
[0054] The polymerization method of the monomer composition (B0) in step 1 may be either bulk polymerization or partition polymerization (dropping polymerization). From the viewpoint of obtaining a resin composition (X) having excellent uniformity (in which the polymer of the monomer composition (BO) is uniformly dispersed), partition polymerization (dropping polymerization) is preferred.
[0055] In step 1, the method for mixing the monomer composition (B0) with the crystalline vinyl resin (C) may be a commonly used known method, and a solvent (toluene, xylene, ethyl acetate, tetrahydrofuran, methyl ethyl ketone, etc.) may be used if necessary. The mixing apparatus includes a batch type mixing apparatus such as a reaction vessel (e.g., an autoclave) and a continuous type mixing apparatus. A batch type mixing apparatus is preferred because it is easy to adjust the pressure, such as by increasing or decreasing the pressure.
[0056] When the monomer composition (B0) is polymerized in the presence of the crystalline vinyl resin (C), the monomer composition (B0) may be polymerized under pressure. When the polymerization is performed under pressure, the pressure is preferably 0.1 to 0.5 MPa, and more preferably 0.3 to 0.4 MPa.
[0057] From the viewpoints of obtaining a resin composition (X) having excellent uniformity, excellent productivity, and good heat-resistant storage stability, the polymerization temperature in step 1 is preferably 110°C to 190°C. The polymerization temperature is more preferably 120°C to 190°C, further preferably 130°C to 190°C, and particularly preferably 140°C to 170°C. When the polymerization temperature is 190°C or lower, the crystalline vinyl resin (C) is less likely to decompose, and the heat-resistant storage stability of the toner binder can be improved. When the polymerization temperature is 110°C or higher, the viscosity of the crystalline vinyl resin (C) is low, and the uniformity between the crystalline vinyl resin (C) and the monomer composition (B0) can be improved, making it possible to obtain a resin composition (X) having even better uniformity.
[0058] The weight ratio of the crystalline vinyl resin (C) used in step 1 is preferably 30% by weight or more, more preferably 40% by weight or more, and preferably 80% by weight or less, more preferably 70% by weight or less, based on the total weight of the crystalline vinyl resin (C) and the monomer composition (B0). When the weight ratio of the crystalline vinyl resin (C) is 30% by weight or more and 80% by weight or less, the low-temperature fixing property, heat-resistant storage stability, hot offset resistance and image strength of the toner binder can be improved.
[0059] Step 1 may include other steps in addition to the polymerization step. There are no particular limitations on the other steps, and any steps that are generally carried out in the production process of a toner binder may be used. Examples of other processes include a process of reducing the pressure in the reaction system after the polymerization process in order to remove the organic solvent, initiator decomposition residues, etc. (pressure reduction process), and a process of taking out the toner binder obtained by the polymerization process and pulverizing it (pulverization process).
[0060] The temperature in the decompression step is preferably 110 to 190°C, more preferably 130 to 190°C, and even more preferably 140 to 170°C.
[0061] The degree of pressure reduction in the pressure reduction step is preferably 0.01 to 30 kPa, more preferably 0.05 to 20 kPa, further preferably 0.08 to 10 kPa, particularly preferably 0.1 to 5 kPa, from the viewpoints of heat resistance storage stability, hot offset resistance and productivity of the toner binder.
[0062] The resin composition (X) obtained by polymerizing a monomer composition (B0) containing a monomer (b1) having a vinyl group in the presence of a crystalline vinyl resin (C) may contain, in addition to the polymer of the crystalline vinyl resin (C) and the monomer composition (B0), a compound in which the polymer of the monomer composition (B0) is bonded to the crystalline vinyl resin (C) and a compound in which a part of the monomer composition (B0) is bonded to the crystalline vinyl resin (C), and the like.
[0063] [Process 2] Step 2 is a step of mixing the resin composition (X) and the amorphous polyester resin (A). In step 2, by mixing the resin composition (X) obtained in step 1 with the amorphous polyester (A), it is possible to provide a toner binder that satisfies all of the low-temperature fixing property, hot offset resistance, fixing width (difference between low-temperature fixing temperature and hot offset resistance temperature), winding property, heat-resistant storage stability, and image strength.
[0064] [Amorphous polyester resin (A)] Examples of the amorphous polyester resin (A) include polyester resins having an alcohol component (ax) and a carboxylic acid component (ay) as constituent monomers.
[0065] Examples of the alcohol component (ax) include an unsaturated alcohol component (ax1) and a saturated alcohol component (ax2), etc. The alcohol component (ax1) may be used alone or in combination of two or more.
[0066] Examples of the unsaturated alcohol (ax1) include unsaturated monoalcohols having 2 to 30 carbon atoms, and unsaturated diols having 2 to 30 carbon atoms. Specific examples include 2-propen-1-ol, oleyl alcohol, 2-hydroxyethyl methacrylate, and ricinoleyl alcohol.
[0067] Examples of the saturated alcohol component (ax2) include monools (ax21), diols (ax22), and trihydric or higher polyols (ax23).
[0068] Examples of the monool (ax21) include linear or branched alkyl alcohols having 1 to 30 carbon atoms (methanol, ethanol, isopropanol, dodecyl alcohol, myristyl alcohol, cetyl alcohol, stearyl alcohol, behenyl alcohol, etc.). Among these monools, linear alkyl alcohols having 8 to 24 carbon atoms are preferred, and dodecyl alcohol, myristyl alcohol, stearyl alcohol, and behenyl alcohol are more preferred. These may be used alone or in combination of two or more.
[0069] Examples of the diol (ax22) include alkylene glycols having 2 to 36 carbon atoms (ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, etc.) (ax221); alkylene ether glycols having 4 to 36 carbon atoms (diethylene glycol, triethylene glycol, dipropylene glycol, polyethylene glycol, etc.). alicyclic diols having 6 to 36 carbon atoms (1,4-cyclohexanedimethanol, hydrogenated bisphenol A, etc.) (ax223); (poly)oxyalkylene adducts of the above alicyclic diols (preferably the number of moles added = 1 to 30) (ax224); aromatic diols [alkylene oxide adducts of monocyclic dihydric phenols (e.g. hydroquinone, etc.) and bisphenols (preferably the number of moles added = 2 to 30)] (ax225); and the like. Among these diols (ax22), from the viewpoints of low-temperature fixability and heat-resistant storage stability, aromatic diols (ax225) are preferred, and alkylene oxide adducts of bisphenols are more preferred. In the alkylene oxide, the alkylene group preferably has 2 to 4 carbon atoms (eg, ethylene oxide, propylene oxide, butylene oxide, and tetrahydrofuran).
[0070] An alkylene oxide adduct of a bisphenol is generally obtained by adding an alkylene oxide (hereinafter, "alkylene oxide" may be abbreviated as AO) to a bisphenol. Examples of the bisphenol include those represented by the following general formula (2).
[0071] HO-Ar-P-Ar-OH (2) [In the formula, P represents an alkylene group having 1 to 3 carbon atoms, -SO2-, -O-, -S-, or a direct bond; and Ar represents a phenylene group in which a hydrogen atom may be substituted with a halogen atom or an alkyl group having 1 to 30 carbon atoms.]
[0072] Specific examples of bisphenols include bisphenol A, bisphenol F, bisphenol B, bisphenol AD, bisphenol S, trichlorobisphenol A, tetrachlorobisphenol A, dibromobisphenol F, 2-methylbisphenol A, 2,6-dimethylbisphenol A, and 2,2'-diethylbisphenol F, and two or more of these can be used in combination.
[0073] The alkylene oxide added to these bisphenols is preferably an alkylene oxide having 2 to 4 carbon atoms, and specific examples thereof include ethylene oxide (hereinafter, "ethylene oxide" may be abbreviated as EO), propylene oxide (hereinafter, "propylene oxide" may be abbreviated as PO), butylene oxide, tetrahydrofuran, and a combination of two or more of these.
[0074] Among these, EO and / or PO are preferred from the viewpoint of improving the heat-resistant storage stability and low-temperature fixability of the toner binder. The number of moles of AO added is preferably 2 to 30 moles, more preferably 2 to 10 moles, from the viewpoint of the heat-resistant storage stability and low-temperature fixability. Among the alkylene oxide adducts of bisphenols, preferred from the viewpoint of toner fixing property are EO and / or PO adducts of bisphenol A (average number of moles added is preferably 2 to 4, and more preferably 2 to 3).
[0075] Examples of the trihydric or higher polyols (ax23) include aliphatic polyhydric alcohols having 3 to 36 carbon atoms and a valence of tri or higher (ax231), sugars and derivatives thereof (ax232), (poly)oxyalkylene ethers of aliphatic polyhydric alcohols (the number of oxyalkylene units is preferably 1 to 30) (ax233), polyoxyalkylene ethers of trisphenols (trisphenol PA, etc.) (the number of oxyalkylene units is preferably 2 to 30) (ax234), and polyoxyalkylene ethers of novolak resins (including phenol novolak and cresol novolak, etc., the average degree of polymerization is preferably 3 to 60) (the number of oxyalkylene units is preferably 2 to 30) (ax235).
[0076] Examples of the aliphatic polyhydric alcohols (ax231) having 3 to 36 carbon atoms and a valence of three or more include alkane polyols and their intramolecular or intermolecular dehydration products, such as glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, sorbitan, polyglycerin, and dipentaerythritol.
[0077] Examples of sugars and their derivatives (ax232) include sucrose and methyl glucoside.
[0078] The alcohol component (ax) as a constituent unit of the amorphous polyester resin (A) is preferably an aromatic diol (ax225), more preferably an alkylene oxide adduct of a bisphenol (the number of AO units is preferably 2 to 5), and further preferably an alkylene oxide adduct of bisphenol A (the number of AO units is preferably 2 to 3).
[0079] The carboxylic acid component (ay) includes an unsaturated carboxylic acid component (ay1) and a saturated carboxylic acid component (ay2). The carboxylic acid component (ay) may be used alone or in combination of two or more kinds.
[0080] Examples of the unsaturated carboxylic acid component (ay1) include unsaturated monocarboxylic acids (ay11), unsaturated dicarboxylic acids (ay12), and anhydrides and lower alkyl esters of these acids.
[0081] Examples of the unsaturated monocarboxylic acid (ay11) include unsaturated monocarboxylic acids having 2 to 30 carbon atoms, and specific examples thereof include acrylic acid, methacrylic acid, crotonic acid, isocrotonic acid, 3-butenoic acid, angelic acid, tiglic acid, 4-pentenoic acid, 2-ethyl-2-butenoic acid, 10-undecenoic acid, 2,4-hexadienoic acid, myristoleic acid, palmitoleic acid, sapienic acid, oleic acid, elaidic acid, vaccenic acid, gadoleic acid, eicosenoic acid, erucic acid, and nervonic acid.
[0082] Examples of the unsaturated dicarboxylic acid (ay12) include alkene dicarboxylic acids having 4 to 50 carbon atoms, and specific examples thereof include alkenylsuccinic acids such as dodecenylsuccinic acid, maleic acid, fumaric acid, citraconic acid, mesaconic acid, itaconic acid, and glutaconic acid.
[0083] Examples of the saturated carboxylic acid component (ay2) include aromatic carboxylic acids (ay21) and aliphatic carboxylic acids (ay22). The saturated carboxylic acid component (ay2) may be used alone or in combination of two or more.
[0084] Examples of the aromatic carboxylic acid (ay21) include aromatic monocarboxylic acids having 7 to 37 carbon atoms (benzoic acid, toluic acid, 4-ethylbenzoic acid, 4-propylbenzoic acid, etc.), aromatic dicarboxylic acids having 8 to 36 carbon atoms (phthalic acid, isophthalic acid, terephthalic acid, naphthalenedicarboxylic acid, etc.), and aromatic polycarboxylic acids having 9 to 20 carbon atoms and having three or more valences (trimellitic acid, pyromellitic acid, etc.). Examples of the aliphatic carboxylic acid (ay22) include aliphatic monocarboxylic acids having 2 to 50 carbon atoms (acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, enanthic acid, caprylic acid, pelargonic acid, capric acid, lauric acid, myristic acid, palmitic acid, margaric acid, stearic acid, behenic acid, etc.), aliphatic dicarboxylic acids having 2 to 50 carbon atoms (oxalic acid, malonic acid, succinic acid, adipic acid, oleaginic acid, sebacic acid, etc.), and aliphatic tricarboxylic acids having 6 to 36 carbon atoms (hexanetricarboxylic acid, etc.).
[0085] The saturated carboxylic acid component (ay2) may be an anhydride or a lower alkyl (having 1 to 4 carbon atoms) ester (such as a methyl ester, an ethyl ester, or an isopropyl ester) of these carboxylic acids.
[0086] The carboxylic acid component (ay) as a structural unit of the amorphous polyester resin (A) is preferably a saturated carboxylic acid component (ay2), more preferably an aromatic carboxylic acid (ay21). From the viewpoint of achieving both low temperature fixing properties and hot offset resistance of the toner binder, aromatic monocarboxylic acids having 7 to 37 carbon atoms, aliphatic dicarboxylic acids having 2 to 50 carbon atoms, aromatic dicarboxylic acids having 8 to 20 carbon atoms, and trivalent or higher aromatic polycarboxylic acids having 9 to 20 carbon atoms are preferred. From the viewpoint of improving the heat resistance storage stability of the toner binder, more preferred are adipic acid, alkyl succinic acid, terephthalic acid, isophthalic acid, trimellitic acid, pyromellitic acid, and combinations thereof. Particularly preferred are adipic acid, terephthalic acid, trimellitic acid, and combinations thereof. Also, anhydrides and lower alkyl esters of these acids may be used.
[0087] From the viewpoint of amorphousness, the amorphous polyester resin (A) preferably contains two or more kinds of carboxylic acid components (ay) as constituent monomers, and more preferably contains three or more kinds of carboxylic acid components (ay) as constituent monomers.
[0088] As the amorphous polyester resin (A), a polyester resin having a polyoxyalkylene ether of a bisphenol (having 2 to 30 AO units) as a constituent monomer as the alcohol component (ax) and at least one selected from terephthalic acid, adipic acid and trimellitic anhydride as a constituent monomer as the carboxylic acid component (ay) is preferred.
[0089] In this specification, the bond of the aromatic ring is not taken into consideration when determining whether it is an unsaturated carboxylic acid component (ay1) or a saturated carboxylic acid component (ay2). That is, a compound in which the portion other than the aromatic ring portion is an unsaturated carboxylic acid is determined to be an unsaturated carboxylic acid component (ay1), and a compound in which the portion other than the aromatic ring portion is a saturated carboxylic acid is determined to be a saturated carboxylic acid component (ay2). Similarly, the aromatic ring bonds are not taken into consideration when determining whether a compound is an unsaturated alcohol component (ax1) or a saturated alcohol component (ax1). In other words, a compound in which the part other than the aromatic ring portion is an unsaturated alcohol component (ax1) is determined to be an unsaturated alcohol component, and a compound in which the part other than the aromatic ring portion is a saturated alcohol component (ax2).
[0090] From the viewpoint of improving the heat-resistant storage stability, low-temperature fixability, and image strength of the toner binder, it is preferable that the amorphous polyester resin (A) is a polyester resin having, as constituent monomers, an alcohol component (ax-1) containing 80 mol % or more of an aromatic diol based on the total number of moles of the alcohol component (ax) and a carboxylic acid component (ay-1) containing 80 mol % or more of an aromatic dicarboxylic acid based on the total number of moles of the carboxylic acid component (ay).
[0091] The amorphous polyester resin (A) can be obtained, for example, by polycondensing an alcohol component (ax) and a carboxylic acid component (ay). The reaction temperature during polycondensation is preferably 150 to 280°C, more preferably 160 to 250°C, and even more preferably 170 to 235°C. From the viewpoint of ensuring the polycondensation reaction, the reaction time is preferably 30 minutes or more, more preferably 2 to 40 hours. It is also effective to reduce the pressure in order to improve the reaction rate at the end of the reaction.
[0092] In the polycondensation, an esterification catalyst can be used, if necessary. Examples of the esterification catalyst include tin-containing catalysts (e.g., dibutyltin oxide), antimony trioxide, titanium-containing catalysts (e.g., titanium alkoxide, potassium oxalate titanate, titanium terephthalate, titanium alkoxide terephthalate, catalysts described in JP-A-2006-243715 {titanium diisopropoxy bis(triethanol aminate), titanium dihydroxy bis(triethanol aminate), titanium monohydroxy tris(triethanol aminate), titanyl bis(triethanol aminate) and their intramolecular polycondensates, etc.}, catalysts described in JP-A-2007-11307 (titanium tributoxy terephthalate, titanium triisopropoxy terephthalate, and titanium diisopropoxy diterephthalate, etc.) and titanium diisopropoxy bistriethanol aminate), zirconium-containing catalysts (e.g., zirconyl acetate), and zinc acetate. Among these, titanium-containing catalysts are preferred.
[0093] A stabilizer may be added to obtain polyester polymerization stability, such as hydroquinone, methylhydroquinone, 4-tert-butylcatechol, 4-methoxyphenol, 2-tert-butyl-4-methoxyphenol, 2,6-di-tert-butyl-4-methoxyphenol, and hindered phenol compounds.
[0094] The charging ratio of the alcohol component (ax) and the carboxylic acid component (ay) is preferably 1 / 2 to 2 / 1, more preferably 1 / 1.3 to 1.5 / 1, and further preferably 1 / 1.2 to 1.4 / 1, in terms of the molar ratio of hydroxyl groups to carboxyl groups [OH] / [COOH].
[0095] From the viewpoints of low-temperature fixability and heat-resistant storage stability, the glass transition temperature (Tg) of the amorphous polyester resin (A) is preferably 55° C. or higher, more preferably 57° C. or higher, and preferably 70° C. or lower, more preferably 65° C. or lower. The glass transition temperature can be measured, for example, by using a DSC Q20 manufactured by TA Instruments Co., Ltd., according to the method (DSC method) specified in ASTM D3418-82.
[0096] The Mw of the amorphous polyester resin (A) is preferably from 2,000 to 200,000, more preferably from 2,500 to 100,000, and even more preferably from 3,000 to 60,000, from the viewpoints of low-temperature fixability, heat-resistant storage stability, and image strength. The Mw of the amorphous polyester resin (A) can be measured by GPC in the same manner as in the above-mentioned crystalline vinyl resin (C).
[0097] The acid value of the amorphous polyester resin (A) is preferably 30 mgKOH / g or less, more preferably 25 mgKOH / g or less, from the viewpoints of low-temperature fixability, heat-resistant storage stability, and image strength. The acid value of the amorphous polyester resin (A) can be measured by the method specified in JIS K0070.
[0098] From the viewpoint of low-temperature fixability and heat-resistant storage stability, the hydroxyl value of the amorphous polyester resin (A) is preferably 10 mgKOH / g or more, more preferably 20 mgKOH / g or more, and is preferably 70 mgKOH / g or less, more preferably 60 mgKOH / g or less. The hydroxyl value of the amorphous polyester resin (A) can be measured by the method specified in JIS K0070.
[0099] The softening point of the amorphous polyester resin (A) measured with a flow tester is preferably from 80 to 170°C, more preferably from 85 to 165°C, and particularly preferably from 90 to 160°C.
[0100] The softening point is measured by the following method. Using a constant test force extrusion-type capillary rheometer flow tester {e.g., CFT-500D, manufactured by Shimadzu Corporation}, 1 g of the test sample is heated at a temperature increase rate of 6°C / min while applying a load of 1.96 MPa with the plunger and extruding it from a nozzle of 1 mm diameter and 1 mm length. A graph of "plunger depression (flow value)" vs. "temperature" is then drawn, and the temperature corresponding to half the maximum plunger depression is read from the graph. This value (the temperature at which half of the test sample has flowed out) is taken as the softening point.
[0101] Two or more types of amorphous polyester resins (A) may be used in step 2. When two or more types of (A) are used, two or more types having different softening points may be used in combination.
[0102] From the viewpoint of excellent hot offset resistance, it is preferable to use the amorphous polyester resin (A) and the resin composition (X) that satisfy the following formula (1). |SP A -SP X |≦1.1 (1) [However, SP A is the solubility parameter (cal / cm) of polyester resin (A). 3 ) 1 / 2 represents SP X is the solubility parameter (cal / cm) of the resin composition (X). 3 ) 1 / 2 In this specification, the solubility parameter may be referred to as the SP value. The SP value (cal / cm 3 ) 1 / 2is calculated by the method described in Polymer Engineering and Science, Vol. 14, pp. 151-154, by Robert F. Fedors et al., and the SP value of the amorphous polyester resin (A) in the present invention can be calculated by taking an arithmetic average based on the molar fraction of the structure obtained by removing hydroxyl groups from the alcohol component used and hydrogen of the carboxyl group from the carboxylic acid component used. The SP value of the resin composition (X) can be calculated by taking an arithmetic average based on the molar fraction of the structural units in which double bonds have become single bonds for the polymer (B0) and all the monomers used in (C).
[0103] The absolute value of the difference between the SP value of the amorphous polyester resin (A) and the SP value of the resin composition (X) (|SP A -SP X |) is more preferably 1.0 (cal / cm 3 ) 1 / 2 Less than or equal to 0.9 (cal / cm 3 ) 1 / 2 More preferably, it is 0.2 (cal / cm 3 ) 1 / 2 More preferably, 0.5 (cal / cm 3 ) 1 / 2 That's all. |SP A -SP XAn example of a combination of the amorphous polyester resin (A) and the resin composition (X) in which | satisfies the above range is a combination of an amorphous polyester resin (A) [a polyester resin having, as constituent monomers, a polyoxyalkylene ether of a bisphenol (the number of AO units is 2 to 30) and at least one carboxylic acid selected from terephthalic acid, adipic acid, and trimellitic anhydride] and a resin composition (X) {a resin composition obtained by polymerizing a polymerizable composition (B0) [a composition containing one or more selected from styrene, butyl (meth)acrylate, methyl acrylate, (meth)acrylic acid, and acrylonitrile] in the presence of a crystalline vinyl resin (C) [a resin obtained by polymerizing a monomer composition (C0) containing at least one compound selected from behenyl alcohol and stearyl alcohol, and at least one compound selected from (meth)acrylic acid, methyl (meth)acrylate, and (meth)acrylonitrile]}.
[0104] [Mixing method] The mixing ratio of the amorphous polyester resin (A) to 100 parts by weight of the resin composition (X) is not particularly limited, but is preferably 1 part by weight or more, more preferably 5 parts by weight or more, and is preferably 30 parts by weight or less, more preferably 20 parts by weight or less. By making the mixing ratio equal to or more than the lower limit, the winding property can be improved, and by making the mixing ratio equal to or less than the upper limit, the low-temperature fixability can be improved.
[0105] In step 2, the resin composition (X) and the amorphous polyester resin (A) can be mixed using a known mixing device (for example, a twin-screw kneader, a polymerization tank, etc.) The temperature when mixing the resin composition (X) and the amorphous polyester (A) is preferably 100°C to 180°C, more preferably 110°C to 170°C. The mixing time is preferably 1 minute or more, more preferably 2 minutes or more, and is preferably 60 minutes or less, more preferably 30 minutes or less.
[0106] At the time of mixing, a component (D) other than the resin composition (X) and the amorphous polyester resin (A) may be mixed. Examples of the other component (D) include other resins (such as the polymers described in Japanese Patent No. 4493080 and JP-A-06-194876) that are known as resins for toner binders other than the amorphous polyester resin (A), the polymerizable composition (B0), and the crystalline vinyl resin (C). When a resin is contained as the other component (D), the resin may be one type or a mixture of two or more types of resins.
[0107] When the other component (D) is mixed, the timing of mixing is not particularly limited. The component (D) may be mixed together with the resin composition (X) and the amorphous polyester resin (A) when they are mixed, or may be mixed with the mixture obtained by mixing the resin composition (X) and the amorphous polyester resin (A).
[0108] Step 2 may include a step of cooling the resin composition (X) and the amorphous polyester resin (A) after mixing them (cooling step). The cooling step can be performed by a method using a known cooling device, a method of leaving the mixture in a room temperature environment (e.g., 20 to 25°C), or the like.
[0109] [Toner binder] The content of the crystalline vinyl resin (C) in the toner binder obtained by the manufacturing method of the present invention is preferably 30% by weight or more, more preferably 40% by weight or more, based on the weight of the toner binder, and is preferably 75% by weight or less, more preferably 65% by weight or less. When the content of the crystalline vinyl resin (C) in the toner binder is equal to or more than the lower limit, the low temperature fixing property, hot offset resistance and fixing width of the toner binder can be improved. The content of the amorphous polyester resin (A) in the toner binder is preferably 1% by weight or more, more preferably 5% by weight or more, and is preferably 30% by weight or less, more preferably 20% by weight or less, based on the weight of the toner binder. By making the content of the amorphous polyester resin (A) in the toner binder equal to or more than the lower limit, the winding property can be improved, and by making the mixing ratio equal to or less than the upper limit, the low-temperature fixing property can be improved.
[0110] From the viewpoint of low-temperature fixability and heat-resistant storage stability of the toner binder, the glass transition temperature (Tg) of the toner binder obtained by the production method of the present invention is preferably 25° C. to 80° C., more preferably 40 to 65° C. When the toner binder has a Tg of 80° C. or lower, the low-temperature fixability is good, and when the Tg is 25° C. or higher, the heat-resistant storage stability is good. The glass transition temperature (Tg) of the toner binder can be measured, for example, by using a DSCQ20 manufactured by TA Instruments Co., Ltd., according to the method (DSC method) prescribed in ASTM D3418-82.
[0111] The toner binder obtained by the present invention preferably has at least one endothermic peak top temperature (Tmb) in the range of 40 to 100°C. When (Tmb) is in this range, the toner binder has a good balance between low-temperature fixability and heat-resistant storage stability. (Tmb) is preferably 43 to 95°C, more preferably 45 to 90°C, even more preferably 50 to 90°C, and particularly preferably 51 to 88°C. The endothermic peak top temperature (Tmb) can be measured by the same method as the endothermic peak top temperature Tmc of the crystalline vinyl resin (C). In the present invention, the endothermic peak top temperature (Tmb) is preferably the peak top temperature of the endothermic peak derived from the crystalline vinyl resin (C).
[0112] The toner binder obtained by the production method of the present invention has, from the viewpoints of low-temperature fixability, fixing width and heat resistance and heat retention, a half-width of an endothermic peak showing a peak top temperature (Tmb) of preferably 6°C or less, more preferably 5°C or less, and particularly preferably 2 to 5°C. The half-width of the endothermic peak indicating the peak top temperature (Tmb) of the toner binder is defined as the temperature width of the peak at half the height of the maximum peak height from the baseline of the endothermic peak, based on the DSC curve obtained by measuring the peak top temperature (Tmb) of the endothermic peak.
[0113] The acid value of the toner binder obtained by the manufacturing method of the present invention is preferably 40 mgKOH / g or less from the viewpoint of excellent heat-resistant storage stability of the toner. When the acid value is 40 mgKOH / g or less, the peak top temperature Tmb of the endothermic peak increases and the moisture absorption decreases, resulting in good heat-resistant storage stability. The acid value of the toner binder is more preferably 30 mgKOH / g or less, and further preferably 0 to 22 mgKOH / g. The acid value of the toner binder can be adjusted by the acid value of the crystalline vinyl resin (C) and the acid value of the monomer contained in the monomer composition (B0), the content of the monomer having an acid value, etc. The acid value of the toner binder is measured by a method such as JIS K0070.
[0114] The weight average molecular weight (Mw) of the toner binder obtained by the present invention is preferably 5,000 to 200,000, more preferably 10,000 to 200,000, further preferably 50,000 to 200,000, and particularly preferably 75,000 to 190,000, from the viewpoint of achieving both hot offset resistance and low temperature fixability of the toner. The weight average molecular weight of the toner binder can be measured by the same method and conditions as those for the crystalline vinyl resin (C).
[0115] [toner] The toner binder obtained by the production method of the present invention can be used as a material for toner. When producing a toner using the toner binder obtained by the production method of the present invention, one or more known additives selected from a colorant, a release agent, a charge control agent, a fluidizing agent, etc. can be used as necessary in addition to the toner binder.
[0116] As the colorant, all of the dyes and pigments used as toner colorants can be used. For example, carbon black, iron black, Sudan Black SM, Fast Yellow G, Benzidine Yellow, Pigment Yellow, India Fast Orange, Irgasin Red, Paranitroaniline Red, Toluidine Red, Carmine FB, Pigment Orange R, Lake Red 2G, Rhodamine FB, Rhodamine B Lake, Methyl Violet B Lake, Phthalocyanine Blue, Pigment Blue, Brilliant Green, Phthalocyanine Green, Oil Yellow GG, Kayaset YG, Orazol Brown B, and Oil Pink OP can be mentioned, and the colorant may be a single one or a mixture of two or more kinds. In addition, if necessary, magnetic powder (powder of ferromagnetic metals such as iron, cobalt, nickel, etc., or compounds such as magnetite, hematite, and ferrite) can be contained to function as a colorant. The content of the colorant is preferably 1 to 40 parts by weight, more preferably 3 to 10 parts by weight, based on 100 parts by weight of the toner binder. When a magnetic powder is used as the colorant, the content is preferably 20 to 150 parts by weight, more preferably 40 to 120 parts by weight.
[0117] For the release agent, the flow softening point (T 1 / 2
[0033] is preferably 50 to 170°C, and examples thereof include aliphatic hydrocarbon waxes such as polyolefin wax, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax, and oxides thereof, carnauba wax, montan wax, and deacidified waxes thereof, ester wax, fatty acid amides, fatty acids, higher alcohols, fatty acid metal salts, and mixtures thereof.
[0118] Flow softening point [T 1 / 2 The measurement method of is described below. Using a constant test force extrusion capillary rheometer flow tester {e.g., Shimadzu Corporation, CFT-500D}, 1 g of the test sample is heated at a temperature increase rate of 6°C / min. At this time, a load of 1.96 MPa is applied by the plunger, and the sample is extruded from a nozzle with a diameter of 1 mm and a length of 1 mm. A graph of "plunger drop (flow value)" vs. "temperature" is drawn, and the temperature corresponding to half the maximum value of the plunger drop is taken as the flow softening point [T 1 / 2 〕
[0119] Examples of polyolefin waxes include (co)polymers of olefins (e.g., ethylene, propylene, 1-butene, isobutylene, 1-hexene, 1-dodecene, 1-octadecene, and mixtures thereof) [including those obtained by (co)polymerization and those obtained by further thermal degradation thereof] (e.g., low molecular weight polypropylene, low molecular weight polyethylene, low molecular weight polypropylene-polyethylene copolymer), oxides of olefin (co)polymers with oxygen and / or ozone, maleic acid modified products of olefin (co)polymers [e.g., maleic acid and its derivatives (maleic anhydride, monomethyl maleate, monobutyl maleate, dimethyl maleate, etc.) modified products], copolymers of olefins and unsaturated carboxylic acids [(meth)acrylic acid, itaconic acid, maleic anhydride, etc.] and / or unsaturated carboxylic acid alkyl esters [(meth)acrylic acid alkyl (alkyl having 1 to 18 carbon atoms) esters and maleic acid alkyl (alkyl having 1 to 18 carbon atoms) esters, etc.], and the like.
[0120] Examples of microcrystalline waxes include Hi-Mic-2095, Hi-Mic-1090, Hi-Mic-1080, Hi-Mic-1070, Hi-Mic-2065, Hi-Mic-1045, and Hi-Mic-2045 manufactured by Nippon Seiro Co., Ltd.
[0121] Examples of paraffin waxes include Paraffin WAX-155, Paraffin WAX-150, Paraffin WAX-145, Paraffin WAX-140, Paraffin WAX-135, HNP-3, HNP-5, HNP-9, HNP-10, HNP-11, HNP-12, and HNP-51, manufactured by Nippon Seiro Co., Ltd.
[0122] Examples of Fischer-Tropsch wax include Sasolwax C80 manufactured by Sasol and FT-0070 manufactured by Nippon Seiro Co., Ltd.
[0123] An example of carnauba wax is Refined Carnauba Wax Special No. 1 manufactured by Kato Yoko Co., Ltd.
[0124] Examples of the ester wax include fatty acid ester waxes (for example, Nissan Electol WEP-2, WEP-3, WEP-4, WEP-5, and WEP-8 manufactured by NOF Corporation).
[0125] The higher alcohols include aliphatic alcohols having 30 to 50 carbon atoms, such as triacontanol. The fatty acids include fatty acids having 30 to 50 carbon atoms, such as triacontancarboxylic acid.
[0126] Examples of fatty acid amides include Diamid Y and Diamid 200 manufactured by Mitsubishi Chemical Corporation.
[0127] The charge control agent may be either a positively charged charge control agent or a negatively charged charge control agent, and examples of the charge control agent include nigrosine dyes, triphenylmethane dyes containing a tertiary amine as a side chain, quaternary ammonium salts, polyamine resins, imidazole derivatives, polymers containing a quaternary ammonium base, metal-containing azo dyes, copper phthalocyanine dyes, metal salicylic acid salts, boron complexes of benzilic acid, sulfonic acid group-containing polymers, fluorine-containing polymers, and halogen-substituted aromatic ring-containing polymers.
[0128] Examples of the fluidizing agent include silica, titania, alumina, calcium carbonate, fatty acid metal salt, silicone resin particles, and fluororesin particles, and two or more of them may be used in combination. From the viewpoint of the chargeability of the toner, silica is preferred. From the viewpoint of the transferability of the toner, the silica is preferably hydrophobic silica. From the viewpoint of the transferability of the toner, the silica is preferably hydrophobic silica.
[0129] The content of the toner binder in the toner is preferably from 30 to 97% by weight, more preferably from 40 to 95% by weight, and further preferably from 45 to 92% by weight, based on the weight of the toner. The content of the colorant is preferably 0.05 to 60% by weight, more preferably 0.1 to 55% by weight, and further preferably 0.5 to 50% by weight, based on the weight of the toner. The content of the release agent is preferably 0 to 30% by weight, more preferably 0.5 to 20% by weight, and further preferably 1 to 10% by weight, based on the weight of the toner. The content of the charge control agent is preferably 0 to 20% by weight, more preferably 0.1 to 10% by weight, and further preferably 0.5 to 7.5% by weight, based on the weight of the toner. The content of the fluidizing agent is preferably 0 to 10% by weight, more preferably 0 to 5% by weight, and further preferably 0.1 to 4% by weight, based on the weight of the toner. The total content of the additives is preferably 3 to 70% by weight, more preferably 4 to 58% by weight, and further preferably 5 to 50% by weight, based on the toner weight.
[0130] The toner containing the toner binder obtained by the present invention may be obtained by any of known methods such as a kneading and pulverizing method, an emulsion phase inversion method, an emulsion polymerization method, a suspension polymerization method, a solution suspension method, and an emulsion aggregation method. For example, when a toner is obtained by a kneading and pulverizing method, the components constituting the toner except for the fluidizing agent are dry-blended using a Henschel mixer, a Nauta mixer, a Banbury mixer, or the like, and then melt-kneaded using a continuous mixing device such as a twin-screw kneader, an extruder, a continuous kneader, or a three-roll mill, and then coarsely pulverized using a mill or the like, and finally micronized using an air flow type micropulverizer, or the like, and further adjusted in particle size distribution using a classifier such as an elbow jet to form toner particles [preferably particles having a volume average particle size (D50) of 5 to 20 μm], and then the fluidizing agent can be mixed therein to produce the toner.
[0131] The volume average particle size (D50) of the toner particles (toner) can be measured using a Coulter counter [for example, trade name: Multisizer III (manufactured by Beckman Coulter, Inc.)]. Specifically, 0.1 to 5 mL of a surfactant (alkylbenzene sulfonate) is added as a dispersant to 100 to 150 mL of an electrolyte solution, ISOTON-II (manufactured by Beckman Coulter). 2 to 20 mg of a measurement sample is then added, and the electrolyte solution in which the sample is suspended is dispersed for approximately 1 to 3 minutes using an ultrasonic disperser. The volume and number of toner particles are measured using a 50 μm aperture with the measurement device, and the volume distribution and number distribution are calculated. From the distribution obtained, the volume average particle size (D50) (μm), number average particle size (μm), and particle size distribution (volume average particle size / number average particle size) of the toner particles are obtained.
[0132] In addition, when the toner is obtained by the emulsion phase inversion method, the components constituting the toner except for the fluidizing agent are dissolved or dispersed in an organic solvent, and then emulsified by adding water or the like, followed by separation and classification to produce the toner. The volume average particle size of the toner is preferably 3 to 15 μm. The toner containing the toner binder obtained by the manufacturing method of the present invention is mixed with carrier particles such as iron powder, glass beads, nickel powder, ferrite, magnetite, and ferrite coated with resin (acrylic resin, silicone resin, etc.) as necessary, and used as a developer for an electric latent image. When carrier particles are used, the weight ratio of the toner to the carrier particles is preferably 1 / 99 to 99 / 1. Also, the toner can be rubbed against a member such as a charging blade instead of the carrier particles to form an electric latent image. The toner containing the toner binder obtained by the production method of the present invention may be in an embodiment that does not contain carrier particles.
[0133] The toner containing the toner binder obtained by the production method of the present invention is fixed to a support (paper, polyester film, etc.) by a copier, printer, etc. to form a recording material. As a method for fixing to a support, a known heat roll fixing method, flash fixing method, etc. can be used.
[0134] The toner produced by using the toner binder obtained by the production method of the present invention is used for developing electrostatic images or magnetic latent images in electrophotography, electrostatic recording, electrostatic printing, etc. More specifically, it is used for developing electrostatic images or magnetic latent images that are particularly suitable for full color. EXAMPLES
[0135] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. In the following, "parts" refers to parts by weight unless otherwise specified.
[0136] <Method of measuring physical properties> The physical properties of the resin, polymer and toner binder were measured by the following methods.
[0137] [Acid value] The acid value was measured according to the method specified in JIS K0070, except that the measurement solvent was a mixed solvent of acetone, methanol, and toluene (acetone:methanol:toluene=12.5:12.5:75).
[0138] [Hydroxyl value] The hydroxyl value was measured according to the method specified in JIS K0070.
[0139] [Weight average molecular weight] The weight average molecular weight was measured by GPC under the following conditions. Equipment: HLC-8120 [Tosoh Corporation] Column: 2 TSK GEL GMH6 [Tosoh Corporation] Measurement temperature: 40℃ Sample solution: 0.25% by weight in THF solution Mobile phase: Tetrahydrofuran (without polymerization inhibitor) Sample solution injection volume: 100 μL Detector: Refractive index detector Reference material: 12 standard polystyrenes (TSKstandard POLYSTYRENE) (molecular weights: 500, 1,050, 2,800, 5,970, 9,100, 18,100, 37,900, 96,400, 190,000, 355,000, 1,090,000, 2,890,000) [manufactured by Tosoh Corporation] In measuring the weight average molecular weight, a sample was dissolved in THF to a concentration of 0.25% by weight, and the insoluble matter was filtered off using a PTFE filter having an aperture of 1 μm to obtain a sample solution.
[0140] [Glass transition temperature] The glass transition temperature (Tg) was measured by the method (DSC method) specified in ASTM D3418-82 using a DSC Q20 manufactured by TA Instruments, Inc. The measurement conditions for the glass transition temperature are as follows. (Measurement conditions) (1) Heat from 30°C to 150°C at 20°C / min (2) Hold at 150°C for 10 minutes (3) Cool to -35°C at 20°C / min (4) Keep at -35℃ for 10 minutes (5) Heat up to 150°C at 20°C / min. (6) The differential scanning calorimetry curves measured in the process of (5) were analyzed.
[0141] [Endothermic peak top temperature and half-width] The peak top temperature of the endothermic peak and the half-width of the endothermic peak indicating the peak top temperature were measured under the following measurement conditions using a differential scanning calorimeter {"DSCQ20" [manufactured by TA Instruments, Inc.]}. (Measurement conditions) (1) Heat from 20°C to 150°C at 10°C / min (2) Cool from 150°C to 0°C at 10°C / min (3) Heat from 0°C to 150°C at 10°C / min. (4) The differential scanning calorimetry curves measured in the process of (3) were analyzed. The half-width of the endothermic peak indicating the peak top temperature of the crystalline vinyl resin (C) is the temperature width of the peak at half the height from the baseline of the endothermic peak to the maximum peak height, based on the DSC curve obtained by measuring the endothermic peak temperature.
[0142] [Softening point] The softening point was measured by the following method. Using a constant test force extrusion-type capillary rheometer flow tester {Shimadzu Corporation, CFT-500D}, 1 g of the test sample was heated at a heating rate of 6°C / min while applying a load of 1.96 MPa with the plunger and extruding it from a nozzle of 1 mm diameter and 1 mm length. A graph was drawn of "plunger depression (flow value)" vs. "temperature," and the temperature corresponding to half the maximum plunger depression was read from the graph. This value (the temperature at which half of the test sample had flowed out) was taken as the softening point.
[0143] <Production Example 1: Production of amorphous polyester resin (A-1)> In a reaction vessel, 616 parts by weight of a propylene oxide 2-mol adduct of bisphenol A, 161 parts by weight of a propylene oxide 3-mol adduct of bisphenol A, 268 parts by weight of terephthalic acid, 1 part by weight of adipic acid, and 2.5 parts by weight of titanium diisopropoxy bistriethanolamine as a condensation catalyst were placed, and reacted at 220°C for 10 hours under a reduced pressure of 0.5 to 2.5 kPa. The reaction was carried out while distilling off the water produced. After the acid value became 1 mgKOH / g or less, the temperature of the jacket that keeps the reaction layer warm was lowered to cool it to 180°C. Next, 9 parts by weight of trimellitic anhydride was added, and the reaction was carried out for 1 hour. It was further cooled to 150°C, and when the softening point became 100°C, a steel belt cooler was used to take out the amorphous polyester resin (A-1).
[0144] <Production Example 2: Production of amorphous polyester resin (A-2)> In a reaction vessel, 321 parts by weight of an ethylene oxide 2-mol adduct of bisphenol A, 421 parts by weight of a propylene oxide 2-mol adduct of bisphenol A, 272 parts by weight of terephthalic acid, and 2.5 parts by weight of titanium diisopropoxy bistriethanolamine as a condensation catalyst were placed and reacted at 220°C for 10 hours under a reduced pressure of 0.5 to 2.5 kPa. The reaction was carried out while distilling off the water produced. After the acid value became 1 mgKOH / g or less, the temperature of the jacket that keeps the reaction layer warm was lowered to cool it to 180°C. Next, 44 parts by weight of trimellitic anhydride was added and reacted for 1 hour. It was further cooled to 150°C, and when the softening point became 96°C, an amorphous polyester resin (A-2) was taken out using a steel belt cooler.
[0145] <Production Example 3: Production of amorphous polyester resin (A-3)> In a reaction vessel, 7 parts by weight of ethylene oxide 2 moles adduct of bisphenol A, 164 parts by weight of propylene oxide 2 moles adduct of bisphenol A, 580 parts by weight of propylene oxide 3 moles adduct of bisphenol A, 260 parts by weight of terephthalic acid, 1 part by weight of adipic acid, 23 parts by weight of trimellitic anhydride, and 2.5 parts by weight of titanium diisopropoxy bistriethanolamine as a condensation catalyst were placed, and reacted at 220°C for 10 hours under a reduced pressure of 0.5 to 2.5 kPa. The reaction was carried out while distilling off the water produced. After the acid value became 3 mgKOH / g or less, 22 parts by weight of trimellitic anhydride was added. The temperature of the jacket that keeps the reaction layer warm was lowered to cool it to 155°C, and when the softening point reached 110°C, a steel belt cooler was used to take out the amorphous polyester resin (A-3).
[0146] The physical properties of the amorphous polyester resins (A-1) to (A-3) obtained in Production Examples 1 to 3 were measured, and the results are shown in Table 1. Table 1 also shows the alcohol component (ax) and carboxylic acid component (ay) used in the production of each resin.
[0147] [Table 1]
[0148] <Production Example 4: Production of Crystalline Vinyl Resin (C-1)> In an autoclave, 300 parts of behenyl acrylate [manufactured by Nisshoku Techno Fine Chemical Co., Ltd., the same applies below] and 200 parts of xylene were charged and replaced with nitrogen. After heating to 140°C in an open state with stirring, the temperature was raised to 170°C in a sealed state with stirring, and the temperature was controlled at 170°C for 2 hours. A mixed solution of 60 parts of styrene, 60 parts of methyl acrylate, 120 parts of acrylonitrile, 60 parts of methoxypolyethylene glycol acrylate [manufactured by Kyoeisha Chemical Co., Ltd., "Light Acrylate 130A"], 2.4 parts of di-t-butyl peroxide, and 180 parts of xylene was dropped over 2 hours while controlling the temperature inside the autoclave to 170°C, and polymerization was performed. After dropping, the dropping line was washed with 20 parts of xylene. After further holding at the same temperature for 0.5 hours, it was cooled to 70°C, and the reaction rate of behenyl acrylate [monomer (c1)] was confirmed. Since the reaction rate was less than 95%, 1.2 parts of di-t-butyl peroxide was further added to react until the reaction rate reached 95% or more. The solvent was removed at 170° C. for 5 hours under reduced pressure of 0.5 to 2.5 kPa to obtain a crystalline vinyl resin (C-1).
[0149] <Production Example 5: Production of Crystalline Vinyl Resin (C-2)> 150 parts of xylene was charged into the autoclave, and after replacing with nitrogen, the temperature was raised to 170°C in a sealed state under stirring. A mixed solution of 420 parts of behenyl acrylate, 140 parts of styrene, 140 parts of acrylonitrile, 1.4 parts of di-t-butyl peroxide, and 72 parts of xylene was adjusted to 60°C, and while controlling the temperature inside the autoclave to 170°C, it was dropped over 3 hours to polymerize. After dropping, the dropping line was washed with 78 parts of xylene. After further maintaining at the same temperature for 0.5 hours, it was cooled to 70°C and the reaction rate of behenyl alcohol [monomer (c1)] was confirmed. Since the reaction rate was less than 95%, 0.7 parts of di-t-butyl peroxide was further added and reacted until the reaction rate reached 95% or more. The solvent was removed at 170°C for 5 hours under reduced pressure of 0.5 to 2.5 kPa to obtain a crystalline vinyl resin (C-2).
[0150] <Production Example 6: Production of Crystalline Vinyl Resin (C-3)> 138 parts of xylene was charged into the autoclave, and after replacing with nitrogen, the temperature was raised to 165°C in a sealed state under stirring. A mixed solution of 345 parts of behenyl acrylate, 105 parts of stearyl acrylate [manufactured by Kyoeisha Chemical Co., Ltd., the same applies below], 75 parts of styrene, 225 parts of acrylonitrile, 3.7 parts of di-t-butyl peroxide, and 100 parts of xylene was adjusted to 60°C, and while controlling the temperature inside the autoclave to 165°C, it was dropped over 3 hours to polymerize. After dropping, the dropping line was washed with 12 parts of xylene. After further holding at 170°C for 0.5 hours, it was cooled to 70°C and the reaction rate of behenyl alcohol and stearyl acrylate [monomer (c1)] was confirmed. Since the reaction rate was less than 95%, 2.0 parts of di-t-butyl peroxide was further added and reacted until the reaction rate reached 95% or more. The solvent was removed at 170° C. for 5 hours under a reduced pressure of 0.5 to 2.5 kPa to obtain a crystalline vinyl resin (C-3).
[0151] <Production Example 7: Production of Crystalline Vinyl Resin (C-4)> An autoclave was charged with 450 parts of behenyl acrylate and 150 parts of xylene, and the atmosphere was replaced with nitrogen. The temperature was raised to 140°C under open stirring, and then raised to 170°C under sealed stirring, and the temperature was controlled at 170°C for 2 hours. A mixed solution of 233 parts of styrene, 45 parts of methyl acrylate, 3.8 parts of 1,6-hexanediol diacrylate [Kyoeisha Chemical Co., Ltd., "Light Acrylate 1.6HX-A"], 19 parts of methacrylic acid, 1.5 parts of di-t-butyl peroxide, and 85 parts of xylene was dropped over 2 hours while controlling the temperature inside the autoclave to 170°C, and polymerization was performed. After dropping, the dropping line was washed with 15 parts of xylene. After holding at the same temperature for another 0.5 hours, the reaction rate of behenyl alcohol [monomer (c1)] was confirmed after cooling to 70°C, and was 95% or more. The solvent was removed at 170° C. for 5 hours under a reduced pressure of 0.5 to 2.5 kPa to obtain a crystalline vinyl resin (C-4).
[0152] <Production Example 8: Production of Crystalline Vinyl Resin (C-5)> 600 parts of stearyl acrylate and 150 parts of xylene were charged in an autoclave and replaced with nitrogen. After heating to 140°C in an open state with stirring, the temperature was raised to 170°C in a sealed state with stirring, and the temperature was controlled at 170°C for 2 hours. A mixed solution of 65 parts of styrene, 75 parts of methyl methacrylate, 10 parts of acrylic acid, 0.7 parts of di-t-butyl peroxide, and 85 parts of xylene was dropped over 2 hours while controlling the temperature inside the autoclave to 170°C, and polymerization was carried out. After dropping, the dropping line was washed with 15 parts of xylene. After holding at the same temperature for another 0.5 hours, it was cooled to 70°C, and the reaction rate of stearyl acrylate [monomer (c1)] was confirmed to be 95% or more. The solvent was removed at 170°C for 5 hours under reduced pressure of 0.5 to 2.5 kPa to obtain a crystalline vinyl resin (C-5).
[0153] <Production Example 9: Production of Crystalline Vinyl Resin (C-6)> 335 parts of behenyl acrylate and 363 parts of ethyl acetate [manufactured by Sankyo Chemical Co., Ltd., the same applies below] were charged into an autoclave, and after replacing with nitrogen, the temperature was raised to 78°C in a sealed state with stirring. A mixed solution of 50 parts of acrylonitrile, 79 parts of styrene, 15 parts of methyl acrylate, 21 parts of methacrylic acid, 9 parts of 2,2'-azobis(2-methylbutyronitrile) [manufactured by Fujifilm Wako Pure Chemical Co., Ltd., the same applies below], and 112 parts of ethyl acetate was dropped over 2 hours while controlling the temperature inside the autoclave to 78°C to polymerize. After dropping, the dropping line was washed with 25 parts of ethyl acetate. After maintaining the temperature at the same temperature for 5 hours, the temperature inside the autoclave was raised to 92°C over 1 hour. After maintaining the temperature at the same temperature for another 2 hours, the reaction rate of behenyl acrylate [monomer (c1)] was confirmed after cooling to 60°C. Since the reaction rate was less than 95%, the temperature was raised to 80°C, and a mixed solution of 3.0 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) [manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., the same applies below] and 38 parts of ethyl acetate was added dropwise over 1 hour. After the dropwise addition, the mixture was kept at 80°C for 2 hours, and reacted until the reaction rate reached 95% or more. The solvent was removed at 110°C for 6 hours under reduced pressure of 0.5 to 2.5 kPa to obtain a crystalline vinyl resin (C-6).
[0154] <Production Example 10: Synthesis of triacontyl acrylate> In a reaction vessel equipped with a stirrer, a heating / cooling device, a thermometer, an air inlet tube, a pressure reducing device, and a water reducing device, 50 parts of 1-triacontanol, 50 parts of toluene, 12 parts of acrylic acid, and 0.05 parts of hydroquinone were added and stirred to make them uniform. Then, 2 parts of paratoluenesulfonic acid were added, and after stirring for 30 minutes, the mixture was reacted for 5 hours while removing the water generated at 100°C while blowing in air at a flow rate of 30 mL / min. Then, the pressure in the reaction vessel was adjusted to 40 kPa, and the reaction was continued for another 3 hours while removing the water generated. After cooling the reaction solution to room temperature, 30 parts of a 10% by weight aqueous sodium hydroxide solution was added, and the mixture was stirred for 1 hour, and then allowed to stand to separate the organic phase and the aqueous phase. The organic phase was collected by liquid separation and centrifugation, and 0.01 parts of hydroquinone was added, and the solvent was removed under reduced pressure while blowing in air to obtain triacontyl acrylate.
[0155] <Production Example 11: Production of Crystalline Vinyl Resin (C-7)> 375 parts of triacontyl acrylate produced in Production Example 10 and 125 parts of xylene were charged in an autoclave and replaced with nitrogen. After heating to 140°C in an open state with stirring, the temperature was raised to 170°C in a sealed state with stirring, and the temperature was controlled at 170°C for 2 hours. A mixed solution of 163 parts of styrene, 97 parts of butyl acrylate, 100 parts of methyl acrylate, 15 parts of acrylic acid, 2.8 parts of di-t-butyl peroxide, and 118 parts of xylene was dropped over 2 hours while controlling the temperature inside the autoclave to 170°C, and polymerization was performed. After dropping, the dropping line was washed with 7 parts of xylene. After holding at the same temperature for another 0.5 hours, the reaction rate of triacontyl acrylate [monomer (c1)] was confirmed after cooling to 70°C, and was 95% or more. The solvent was removed at 170° C. for 5 hours under a reduced pressure of 0.5 to 2.5 kPa to obtain a crystalline vinyl resin (C-7).
[0156] <Comparative Production Example 1: Production of Crystalline Vinyl Resin (C'-1)> 560 parts of behenyl acrylate and 240 parts of xylene were charged in an autoclave and replaced with nitrogen. After heating to 140°C in an open state with stirring, the temperature was raised to 170°C in a sealed state with stirring, and the temperature was controlled at 170°C for 2 hours. A mixed solution of 140 parts of styrene, 1.4 parts of di-t-butyl peroxide, and 48 parts of xylene was dropped over 2 hours while controlling the temperature inside the autoclave at 170°C to polymerize. After dropping, the dropping line was washed with 12 parts of xylene. After holding at the same temperature for another 0.5 hours, the reaction rate of behenyl alcohol [monomer (c1)] was confirmed after cooling to 100°C and was 95% or more. The solvent was removed at 170°C for 5 hours under reduced pressure of 0.5 to 2.5 kPa to obtain a crystalline vinyl resin (C'-1).
[0157] [Calculation method for the reaction rate of monomer (c1)] The reaction rate (%) of the monomer (c1) in Production Examples 4 to 11 and Comparative Production Example 1 was calculated by a method for identifying the amount of the remaining monomer using NMR. The measurement conditions, sample preparation method, and analysis and calculation methods are as follows. (Measurement conditions) Equipment: Bruker Biospin "AVANCE III HD400" Number of times: 4 Relaxation time: 1 second (Sample preparation) 100 mg of the sample was placed in an NMR tube, and 0.8 mL of a deuterated solvent (e.g., deuterated chloroform) was added to dissolve the resin. (Analysis and Calculation) The reaction rate was calculated from the area of the protons of the monomer (c1) before the reaction, the area of the protons of the remaining monomer (c1), and the area of the protons of the terminal methyl groups of the chain hydrocarbon groups of the monomer (c1) and the crystalline vinyl resin (C) according to the following formula. Reaction rate: 100 x [{area of protons bonded to the double bond carbon of monomer (c1) before reaction / area of protons of terminal methyl groups of linear hydrocarbon groups of monomer (c1) and crystalline vinyl resin (C)} - {area of protons bonded to the double bond carbon of remaining monomer (c1) / area of protons of terminal methyl groups of linear hydrocarbon groups of monomer (c1) and crystalline vinyl resin (C)}] / {area of protons bonded to the double bond carbon of monomer (c1) before reaction / area of protons of terminal methyl groups of linear hydrocarbon groups of monomer (c1) and crystalline vinyl resin (C)} For example, when the monomer (c1) was behenyl acrylate, the protons bonded to the double bond carbon (about 6.4 ppm) and the protons of the terminal methyl groups of the chain hydrocarbon groups (about 0.9 ppm) were used.
[0158] The physical properties of the crystalline vinyl resins (C-1) to (C-7) and (C'-1) obtained in Production Examples 4 to 11 were measured, and the results are shown in Table 2. Table 2 also shows the type and amount of monomer used in the production of each resin, the radical reaction initiator (cs) and its amount, the weight percentage of monomer (c1) in monomer composition (C0), and the weight percentage of monomer (c2) in monomer composition (C0).
[0159] [Table 2]
[0160] <Example 1: Production of toner binder (E-1)> 20 parts of xylene and 60 parts of the crystalline vinyl resin (C-1) obtained in Production Example 4 were charged into an autoclave and replaced with nitrogen. The temperature was raised to 140°C in an open state with stirring (with the lid of the reaction vessel open), and then the reaction vessel was sealed with stirring. A mixed solution (monomer composition B0-1) of 28.6 parts of styrene, 10.8 parts of butyl acrylate, 0.6 parts of acrylic acid, 0.06 parts of di-t-butyl peroxide, and 11 parts of xylene was dropped over 3 hours while controlling the temperature inside the autoclave to 140°C to carry out polymerization. After dropping, the dropping line was washed with 2 parts of xylene. After holding at 140°C for another hour, the temperature was raised to 170°C over 1 hour to decompose the reaction initiator. After cooling to 120°C, the reaction rate of styrene was confirmed to be 95% or more. Next, the solvent was removed at 170°C for 5 hours under a reduced pressure of 0.5 to 2.5 kPa, and then the mixture was cooled to room temperature to obtain a resin composition (X-1) containing a crystalline vinyl resin (C-1) and an amorphous vinyl resin (B-1). The amorphous vinyl resin (B-1) is a polymer of the monomer composition (B0-1). 100 parts of the obtained resin composition (X-1) and 10 parts of the amorphous polyester resin (A-1) were fed to a twin-screw kneader [PCM-30, manufactured by Ikegai Corporation] and kneaded at 110°C for 2 minutes, and then cooled to room temperature to obtain a toner binder (E-1) according to Example 1. When the dispersibility of the amorphous vinyl resin (B-1) was confirmed, it was found that the amorphous vinyl resin (B-1) was dispersed in the toner binder.
[0161] <Example 2: Preparation of toner binder (E-2)> 13 parts of xylene and 50 parts of the crystalline vinyl resin (C-2) obtained in Production Example 5 were charged into an autoclave and replaced with nitrogen. The temperature was raised to 140°C in an open state with stirring, and then the autoclave was sealed with stirring. A mixed solution (monomer composition B0-2) of 35.8 parts of styrene, 13.5 parts of butyl acrylate, 0.75 parts of acrylic acid, 0.1 parts of di-t-butyl peroxide, and 11 parts of xylene was dropped over 3 hours while controlling the temperature inside the autoclave to 140°C to polymerize. After dropping, the dropping line was washed with 2 parts of xylene. After further holding at 140°C for 1 hour, the temperature was raised to 170°C over 1 hour to decompose the reaction initiator. After cooling to 120°C, the reaction rate of styrene was confirmed to be 95% or more. Next, the solvent was removed at 170°C for 5 hours under reduced pressure of 0.5 to 2.5 kPa, and the pressure was returned to normal pressure, and then a resin composition (X-2) was obtained. The resin composition (X-2) was placed in an autoclave and subjected to the next step (mixing step). The resin composition (X-2) was mixed with 10 parts of the amorphous polyester resin (A-1), homogenized at 170°C for 30 minutes, and then cooled to room temperature to obtain a toner binder (E-2) according to Example 2. When the dispersibility of the amorphous vinyl resin (B-2) was confirmed, it was found that the amorphous vinyl resin (B-2) was dispersed in the toner binder. The amorphous vinyl resin (B-2) is a polymer of the monomer composition (B0-2).
[0162] <Example 3: Preparation of toner binder (E-3)> 13 parts of xylene and 40 parts of the crystalline vinyl resin (C-3) obtained in Production Example 6 were charged into an autoclave and replaced with nitrogen. The temperature was raised to 140°C in an open state with stirring, and then the autoclave was sealed with stirring. A mixed solution (monomer composition B0-3) of 42.9 parts of styrene, 16.2 parts of butyl acrylate, 0.9 parts of acrylic acid, 0.09 parts of di-t-butyl peroxide, and 18 parts of xylene was dropped over 3 hours while controlling the temperature inside the autoclave to 150°C to polymerize. After dropping, the dropping line was washed with 2 parts of xylene. After holding at 150°C for another hour, the temperature was raised to 170°C over 1 hour to decompose the reaction initiator. After cooling to 120°C, the reaction rate of styrene was confirmed to be 95% or more. Next, the solvent was removed at 170°C for 5 hours under a reduced pressure of 0.5 to 2.5 kPa, and then the mixture was cooled to room temperature to obtain a resin composition (X-3) containing a crystalline vinyl resin (C-3) and an amorphous vinyl resin (B-3). The amorphous vinyl resin (B-3) is a polymer of the monomer composition (B0-3). 100 parts of the obtained resin composition (X-3) and 10 parts of the amorphous polyester resin (A-1) were fed to a twin-screw kneader and kneaded at 120°C for 2 minutes, and then cooled to room temperature to obtain a toner binder (E-3) according to Example 3. When the dispersibility of the amorphous vinyl resin (B-3) was confirmed, it was found that the amorphous vinyl resin (B-3) was dispersed in the toner binder.
[0163] <Example 4: Preparation of toner binder (E-4)> 12 parts of xylene and 35 parts of the crystalline vinyl resin (C-4) obtained in Production Example 7 were charged into an autoclave and replaced with nitrogen. The temperature was raised to 140°C in an open state with stirring, and then the autoclave was sealed with stirring. A mixed solution (monomer composition B0-4) of 46.5 parts of styrene, 17.6 parts of butyl acrylate, 0.98 parts of acrylic acid, 0.1 parts of di-t-butyl peroxide, and 20 parts of xylene was dropped over 3 hours while controlling the temperature inside the autoclave to 140°C to polymerize. After dropping, the dropping line was washed with 2 parts of xylene. After holding at 140°C for another hour, the temperature was raised to 170°C over 1 hour to decompose the reaction initiator. After cooling to 120°C, the reaction rate of styrene was confirmed to be 95% or more. Next, the solvent was removed at 170°C for 5 hours under a reduced pressure of 0.5 to 2.5 kPa, and then the mixture was cooled to room temperature to obtain a resin composition (X-4) containing a crystalline vinyl resin (C-4) and an amorphous vinyl resin (B-4). The amorphous vinyl resin (B-4) is a polymer of the monomer composition (B0-4). 100 parts of the obtained resin composition (X-4) and 10 parts of the amorphous polyester resin (A-1) were fed to a twin-screw kneader and kneaded at 120°C for 2 minutes, and then cooled to room temperature to obtain a toner binder (E-4) according to Example 4. When the dispersibility of the amorphous vinyl resin (B-4) was confirmed, it was found that the amorphous vinyl resin (B-4) was dispersed in the toner binder.
[0164] <Example 5: Preparation of toner binder (E-5)> 19 parts of xylene and 45 parts of the crystalline vinyl resin (C-5) obtained in Production Example 8 were charged into an autoclave and replaced with nitrogen. The temperature was raised to 140°C in an open state with stirring, and then the autoclave was sealed with stirring. A mixed solution (monomer composition B0-5) of 39.3 parts of styrene, 14.9 parts of butyl acrylate, 0.83 parts of acrylic acid, 0.1 parts of di-t-butyl peroxide, and 21 parts of xylene was dropped over 3 hours while controlling the temperature inside the autoclave to 160°C to polymerize. After dropping, the dropping line was washed with 3 parts of xylene. After holding at 160°C for another 1 hour, the temperature was raised to 170°C over 1 hour to decompose the reaction initiator. After cooling to 120°C, the reaction rate of styrene was confirmed to be 95% or more. Next, the solvent was removed at 170°C for 5 hours under a reduced pressure of 0.5 to 2.5 kPa, and then the mixture was cooled to room temperature to obtain a resin composition (X-5) containing a crystalline vinyl resin (C-5) and an amorphous vinyl resin (B-5). The amorphous vinyl resin (B-5) is a polymer of the monomer composition (B0-5). 100 parts of the obtained resin composition (X-5) and 10 parts of the amorphous polyester resin (A-1) were fed to a twin-screw kneader and kneaded at 120°C for 2 minutes, and then cooled to room temperature to obtain a toner binder (E-5) according to Example 5. When the dispersibility of the amorphous vinyl resin (B-5) was confirmed, it was found that the amorphous vinyl resin (B-1) was dispersed in the toner binder.
[0165] <Example 6: Preparation of toner binder (E-6)> 18 parts of xylene and 70 parts of the crystalline vinyl resin (C-6) obtained in Production Example 9 were charged into an autoclave and replaced with nitrogen. The temperature was raised to 140°C in an open state with stirring, and then the autoclave was sealed with stirring. A mixed solution (monomer composition B0-6) of 21.5 parts of styrene, 8.1 parts of butyl acrylate, 0.45 parts of acrylic acid, 0.06 parts of di-t-butyl peroxide, and 6 parts of xylene was dropped over 3 hours while controlling the temperature inside the autoclave to 140°C to polymerize. After dropping, the dropping line was washed with 2 parts of xylene. After holding at 140°C for another hour, the temperature was raised to 170°C over 1 hour to decompose the reaction initiator. After cooling to 120°C, the reaction rate of styrene was confirmed to be 95% or more. Next, the solvent was removed at 170°C for 5 hours under a reduced pressure of 0.5 to 2.5 kPa, and then the mixture was cooled to room temperature to obtain a resin composition (X-6) containing a crystalline vinyl resin (C-6) and an amorphous vinyl resin (B-6). The amorphous vinyl resin (B-6) is a polymer of the monomer composition (B0-6). 100 parts of the obtained resin composition (X-6) and 10 parts of the amorphous polyester resin (A-1) were fed to a twin-screw kneader and kneaded at 100°C for 2 minutes, and then cooled to room temperature to obtain a toner binder (E-6) according to Example 6. When the dispersibility of the amorphous vinyl resin (B-6) was confirmed, it was found that the amorphous vinyl resin (B-6) was dispersed in the toner binder.
[0166] <Example 7: Preparation of toner binder (E-7)> 27 parts of xylene and 80 parts of the crystalline vinyl resin (C-7) obtained in Production Example 11 were charged into an autoclave and replaced with nitrogen. The temperature was raised to 140°C in an open state with stirring, and then the autoclave was sealed with stirring. A mixed solution (monomer composition B0-7) of 14.3 parts of styrene, 5.4 parts of butyl acrylate, 0.3 parts of acrylic acid, 0.04 parts of di-t-butyl peroxide, and 5 parts of xylene was dropped over 3 hours while controlling the temperature inside the autoclave to 170°C to carry out polymerization. After dropping, the dropping line was washed with 2 parts of xylene. The reaction was further maintained at 170°C for 1 hour to decompose the reaction initiator. After cooling to 120°C, the reaction rate of styrene was confirmed to be 95% or more. Next, the solvent was removed at 170°C for 5 hours under a reduced pressure of 0.5 to 2.5 kPa, and then the mixture was cooled to room temperature to obtain a resin composition (X-7) containing a crystalline vinyl resin (C-7) and an amorphous vinyl resin (B-7). The amorphous vinyl resin (B-7) is a polymer of the monomer composition (B0-7). 100 parts of the obtained resin composition (X-7) and 10 parts of the amorphous polyester resin (A-1) were fed to a twin-screw kneader and kneaded at 100°C for 2 minutes, and then cooled to room temperature to obtain a toner binder (E-7) according to Example 7. When the dispersibility of the amorphous vinyl resin (B-7) was confirmed, it was found that the amorphous vinyl resin (B-7) was dispersed in the toner binder.
[0167] <Example 8: Preparation of toner binder (E-8)> 13 parts of xylene and 40 parts of the crystalline vinyl resin (C-2) obtained in Production Example 5 were charged into an autoclave and replaced with nitrogen. The temperature was raised to 140°C in an open state with stirring, and then the autoclave was sealed with stirring. A mixed solution (monomer composition B0-8) of 45 parts of styrene, 13.8 parts of butyl acrylate, 1.2 parts of acrylic acid, 0.12 parts of di-t-butyl peroxide, and 18 parts of xylene was dropped over 3 hours while controlling the temperature inside the autoclave to 140°C to polymerize. After dropping, the dropping line was washed with 2 parts of xylene. After holding at 140°C for another 1 hour, the temperature was raised to 170°C over 1 hour to decompose the reaction initiator. After cooling to 120°C, the reaction rate of styrene was confirmed to be 95% or more. Next, the solvent was removed at 170°C for 5 hours under reduced pressure of 0.5 to 2.5 kPa, and the pressure was returned to normal pressure, and a resin composition (X-8) was obtained. The resin composition (X-8) was placed in an autoclave and subjected to the next step (mixing step). The obtained resin composition (X-8) was mixed with 10 parts of amorphous polyester resin (A-1), homogenized at 170°C for 30 minutes, and then cooled to room temperature to obtain a toner binder (E-8) according to Example 8. When the dispersibility of the amorphous vinyl resin (B-8) was confirmed, the amorphous vinyl resin (B-8) was dispersed in the toner binder. The amorphous vinyl resin (B-8) is a polymer of the monomer composition (B0-8).
[0168] <Example 9: Preparation of toner binder (E-9)> 13 parts of xylene and 40 parts of the crystalline vinyl resin (C-3) obtained in Production Example 6 were charged into an autoclave and replaced with nitrogen. The temperature was raised to 140°C in an open state with stirring, and then the autoclave was sealed with stirring. The monomer composition B0-8 was dropped over 3 hours while controlling the temperature inside the autoclave to 140°C, and polymerization was carried out. After dropping, the dropping line was washed with 2 parts of xylene. After further holding at 140°C for 1 hour, the temperature was raised to 170°C over 1 hour to decompose the reaction initiator. After cooling to 120°C, the reaction rate of styrene was confirmed to be 95% or more. Next, the solvent was removed at 170°C for 5 hours under a reduced pressure of 0.5 to 2.5 kPa, and the pressure was returned to normal pressure, and a resin composition (X-9) was obtained. The resin composition (X-9) was subjected to the next step (mixing step) in the state of being placed in the autoclave. The obtained resin composition (X-9) was mixed with 10 parts of amorphous polyester resin (A-2), homogenized at 170°C for 30 minutes, and then cooled to room temperature to obtain a toner binder (E-9) according to Example 9. When the dispersibility of the amorphous vinyl resin (B-8) was confirmed, the amorphous vinyl resin (B-8) was dispersed in the toner binder. The amorphous vinyl resin (B-8) is a polymer of the monomer composition (B0-8).
[0169] <Example 10: Preparation of toner binder (E-10)> 13 parts of xylene and 40 parts of the crystalline vinyl resin (C-4) obtained in Production Example 7 were charged into an autoclave and replaced with nitrogen. The temperature was raised to 140°C in an open state with stirring, and then the autoclave was sealed with stirring. The monomer composition B0-8 was dropped over 3 hours while controlling the temperature inside the autoclave to 140°C, and polymerization was carried out. After dropping, the dropping line was washed with 2 parts of xylene. After further holding at 140°C for 1 hour, the temperature was raised to 170°C over 1 hour to decompose the reaction initiator. After cooling to 120°C, the reaction rate of styrene was confirmed to be 95% or more. Next, the solvent was removed at 170°C for 5 hours under a reduced pressure of 0.5 to 2.5 kPa, and the pressure was returned to normal pressure, and a resin composition (X-10) was obtained. The resin composition (X-10) was subjected to the next step (mixing step) in the state of being placed in the autoclave. The obtained resin composition (X-9) was mixed with 10 parts of amorphous polyester resin (A-3), homogenized at 170°C for 30 minutes, and then cooled to room temperature to obtain a toner binder (E-10) according to Example 10. When the dispersibility of the amorphous vinyl resin (B-8) was confirmed, the amorphous vinyl resin (B-8) was dispersed in the toner binder. The amorphous vinyl resin (B-8) is a polymer of the monomer composition (B0-8).
[0170] <Example 11: Preparation of toner binder (E-11)> 13 parts of xylene and 40 parts of the crystalline vinyl resin (C-2) obtained in Production Example 5 were charged into an autoclave and replaced with nitrogen. The temperature was raised to 140°C in an open state with stirring, and then the autoclave was sealed with stirring. A mixed solution (monomer composition B0-9) of 22.2 parts of styrene, 12 parts of butyl acrylate, 15 parts of acrylonitrile, 10.8 parts of methyl acrylate, 0.12 parts of di-t-butyl peroxide, and 18 parts of xylene was dropped over 3 hours while controlling the temperature inside the autoclave to 130°C, to carry out polymerization. After dropping, the dropping line was washed with 2 parts of xylene. After holding at 130°C for another 1 hour, the temperature was raised to 170°C over 1 hour to decompose the reaction initiator. After cooling to 120°C, the reaction rate of styrene was confirmed to be 95% or more. Next, the solvent was removed at 170° C. for 5 hours under a reduced pressure of 0.5 to 2.5 kPa, and then the mixture was cooled to room temperature to obtain a resin composition (X-11) containing a crystalline vinyl resin (C-2) and an amorphous vinyl resin (B-9). 100 parts of the obtained resin composition (X-11) and 10 parts of the amorphous polyester resin (A-2) were fed to a twin-screw kneader, kneaded at 120°C for 2 minutes, and then cooled to room temperature to obtain a toner binder (E-11) according to Example 11. When the dispersibility of the amorphous vinyl resin (B-9) was confirmed, the amorphous vinyl resin (B-9) was dispersed in the toner binder. The amorphous vinyl resin (B-9) is a polymer of the monomer composition (B0-9).
[0171] <Example 12: Preparation of toner binder (E-12)> 13 parts of xylene and 40 parts of the crystalline vinyl resin (C-3) obtained in Production Example 6 were charged into an autoclave and replaced with nitrogen. The temperature was raised to 140°C in an open state under stirring, and then the autoclave was sealed under stirring. The monomer composition B0-9 was added dropwise over 3 hours while controlling the temperature inside the autoclave to 140°C to polymerize. After the addition, the dropping line was washed with 2 parts of xylene. After further maintaining at 140°C for 1 hour, the temperature was raised to 170°C over 1 hour to decompose the reaction initiator. After cooling to 120°C, the reaction rate of styrene was confirmed to be 95% or more. Next, the solvent was removed at 170°C for 5 hours under a reduced pressure of 0.5 to 2.5 kPa, and then cooled to room temperature to obtain a resin composition (X-12) containing the crystalline vinyl resin (C-3) and the amorphous vinyl resin (B-9). 100 parts of the obtained resin composition (X-12) and 10 parts of the amorphous polyester resin (A-3) were fed to a twin-screw kneader, kneaded at 120°C for 2 minutes, and then cooled to room temperature to obtain a toner binder (E-12) according to Example 12. When the dispersibility of the amorphous vinyl resin (B-9) was confirmed, the amorphous vinyl resin (B-9) was dispersed in the toner binder. The amorphous vinyl resin (B-9) is a polymer of the monomer composition (B0-9).
[0172] <Example 13: Preparation of toner binder (E-13)> 13 parts of xylene and 40 parts of the crystalline vinyl resin (C-4) obtained in Production Example 7 were charged into an autoclave and replaced with nitrogen. The temperature was raised to 140°C in an open state under stirring, and then the autoclave was sealed under stirring. The monomer composition B0-9 was added dropwise over 3 hours while controlling the temperature inside the autoclave to 140°C to polymerize. After the addition, the dropping line was washed with 2 parts of xylene. After further holding at 140°C for 1 hour, the temperature was raised to 170°C over 1 hour to decompose the reaction initiator. After cooling to 120°C, the reaction rate of styrene was confirmed to be 95% or more. Next, the solvent was removed at 170°C for 5 hours under reduced pressure of 0.5 to 2.5 kPa, and then cooled to room temperature to obtain a resin composition (X-13) containing a crystalline vinyl resin (C-4) and an amorphous vinyl resin (B-9). 100 parts of the obtained resin composition (X-13) and 10 parts of the amorphous polyester resin (A-1) were fed to a twin-screw kneader, kneaded at 120°C for 2 minutes, and then cooled to room temperature to obtain a toner binder (E-13) according to Example 12. When the dispersibility of the amorphous vinyl resin (B-9) was confirmed, the amorphous vinyl resin (B-9) was dispersed in the toner binder. The amorphous vinyl resin (B-9) is a polymer of the monomer composition (B0-9).
[0173] <Example 14: Preparation of toner binder (E-14)> 13 parts of xylene and 40 parts of the crystalline vinyl resin (C-2) obtained in Production Example 5 were charged into an autoclave and replaced with nitrogen. The temperature was raised to 140°C in an open state under stirring, and then the autoclave was sealed under stirring. The monomer composition B0-9 was added dropwise over 3 hours while controlling the temperature inside the autoclave to 140°C to polymerize. After the dropwise addition, the dropping line was washed with 2 parts of xylene. After further maintaining at 140°C for 1 hour, the temperature was raised to 170°C over 1 hour to decompose the reaction initiator. After cooling to 120°C, the reaction rate of styrene was confirmed to be 95% or more. The solvent was removed at 170°C for 5 hours under a reduced pressure of 0.5 to 2.5 kPa, and then cooled to room temperature to obtain a resin composition (X-14) containing the crystalline vinyl resin (C-2) and the amorphous vinyl resin (B-9). 100 parts of the obtained resin composition (X-14) and 20 parts of the amorphous polyester resin (A-1) were fed to a twin-screw kneader, kneaded at 120°C for 2 minutes, and then cooled to room temperature to obtain a toner binder (E-14) according to Example 14. When the dispersibility of the amorphous vinyl resin (B-9) was confirmed, the amorphous vinyl resin (B-9) was dispersed in the toner binder. The amorphous vinyl resin (B-9) is a polymer of the monomer composition (B0-9).
[0174] <Example 15: Preparation of toner binder (E-15)> 13 parts of xylene and 40 parts of the crystalline vinyl resin (C-2) obtained in Production Example 5 were charged into an autoclave and replaced with nitrogen. The temperature was raised to 140°C in an open state under stirring, and then the autoclave was sealed under stirring. The monomer composition B0-9 was added dropwise over 3 hours while controlling the temperature inside the autoclave to 140°C to polymerize. After the dropwise addition, the dropping line was washed with 2 parts of xylene. After further maintaining at 140°C for 1 hour, the temperature was raised to 170°C over 1 hour to decompose the reaction initiator. After cooling to 120°C, the reaction rate of styrene was confirmed to be 95% or more. The solvent was removed at 170°C for 5 hours under reduced pressure of 0.5 to 2.5 kPa, and then cooled to room temperature to obtain a resin composition (X-15) containing the crystalline vinyl resin (C-2) and the amorphous vinyl resin (B-9). 100 parts of the obtained resin composition (X-15) and 5 parts of the amorphous polyester resin (A-1) were fed to a twin-screw kneader, kneaded at 120°C for 2 minutes, and then cooled to room temperature to obtain a toner binder (E-15) according to Example 15. When the dispersibility of the amorphous vinyl resin (B-9) was confirmed, the amorphous vinyl resin (B-9) was dispersed in the toner binder. The amorphous vinyl resin (B-9) is a polymer of the monomer composition (B0-9).
[0175] <Comparative Example 1: Production of toner binder (E'-1)> 20 parts of xylene and 60 parts of the crystalline vinyl resin (C'-1) obtained in Comparative Production Example 1 were charged into an autoclave and replaced with nitrogen. The temperature was raised to 140°C in an open state with stirring, and then the autoclave was sealed with stirring. The monomer composition B0-1 (see Example 1) was dropped over 3 hours while controlling the temperature inside the autoclave to 140°C to polymerize. After dropping, the dropping line was washed with 2 parts of xylene. After further maintaining at 140°C for 1 hour, the temperature was raised to 170°C over 1 hour to decompose the reaction initiator. After cooling to 120°C, the reaction rate of styrene was confirmed to be 95% or more. The solvent was removed at 170°C for 5 hours under reduced pressure of 0.5 to 2.5 kPa, and then cooled to room temperature to obtain a resin composition (X'-1). 100 parts of the obtained resin composition (X'-1) and 10 parts of the amorphous polyester resin (A-1) were supplied to a twin-screw kneader, kneaded at 110°C for 2 minutes, and then cooled to room temperature to obtain a toner binder (E'-1) relating to Comparative Example 1.
[0176] <Comparative Example 2: Production of toner binder (E'-2)> 20 parts of xylene was charged into the autoclave and replaced with nitrogen. After heating to 140°C in an open state with stirring, the autoclave was sealed with stirring. A mixed solution (monomer composition B0-10) of 71.5 parts of styrene, 27 parts of butyl acrylate, 1.5 parts of acrylic acid, 0.15 parts of di-t-butyl peroxide, and 11 parts of xylene was dropped over 3 hours while controlling the temperature inside the autoclave to 140°C to polymerize. After dropping, the dropping line was washed with 2 parts of xylene. After holding at 140°C for another 1 hour, the temperature was raised to 170°C over 1 hour to decompose the reaction initiator. After cooling to 120°C, the reaction rate of styrene was confirmed to be 95% or more. The solvent was removed at 170°C for 5 hours under reduced pressure of 0.5 to 2.5 kPa, and then cooled to room temperature to obtain a resin composition (X'-2). 100 parts of the obtained resin composition (X'-2) and 10 parts of the amorphous polyester resin (A-1) were mixed, supplied to a twin-screw kneader, kneaded at 130°C for 2 minutes, and then cooled to room temperature to obtain a toner binder (E'-2) relating to Comparative Example 2.
[0177] <Comparative Example 3: Production of toner binder (E'-3)> 100 parts of the crystalline vinyl resin (C-1) obtained in Production Example 4 and 10 parts of the amorphous polyester resin (A-1) were fed to a twin-screw kneader and kneaded for 2 minutes at 80° C. The mixture obtained after kneading was cooled to obtain a toner binder (E'-3) according to Comparative Example 3.
[0178] <Comparative Example 4: Production of toner binder (E'-4)> 20 parts of xylene and 60 parts of the crystalline vinyl resin (C-1) obtained in Production Example 4 were charged into an autoclave and replaced with nitrogen. The temperature was raised to 140°C in an open state with stirring, and then the autoclave was sealed with stirring. The monomer composition B0-1 was dropped over 3 hours while controlling the temperature inside the autoclave to 140°C, and polymerization was carried out. After dropping, the dropping line was washed with 2 parts of xylene. After further holding at 140°C for 1 hour, the temperature was raised to 170°C over 1 hour to decompose the reaction initiator. After cooling to 120°C, the reaction rate of styrene was confirmed to be 95% or more. The solvent was removed at 170°C for 5 hours under reduced pressure of 0.5 to 2.5 kPa, and then cooled to room temperature to obtain a toner binder (E'-4) according to Comparative Example 4.
[0179] <Comparative Example 5: Production of toner binder (E'-5)> 20 parts of xylene was charged into an autoclave and replaced with nitrogen. After heating to 140°C in an open state with stirring, the autoclave was sealed with stirring. The monomer composition B0-1 was added dropwise over 3 hours while controlling the temperature inside the autoclave at 140°C to polymerize. After dropping, the dropping line was washed with 2 parts of xylene. After holding at 140°C for another hour, the temperature was raised to 170°C over 1 hour to decompose the reaction initiator. After cooling to 120°C, the reaction rate of styrene was confirmed to be 95% or more. The solvent was removed at 170°C for 5 hours under reduced pressure of 0.5 to 2.5 kPa, and then cooled to room temperature to obtain resin (X'-4). 40 parts of the obtained resin (X'-4), 10 parts of amorphous polyester resin (A-1), and 60 parts of the crystalline vinyl resin (C-1) obtained in Manufacturing Example 4 were supplied to a twin-screw kneader, kneaded at 110°C for 2 minutes, and then cooled to room temperature to obtain a toner binder (E'-2) related to Comparative Example 5.
[0180] [Calculation method for styrene reaction rate] The reaction rate (%) of styrene in Examples 1 to 15 and Comparative Examples 1 to 5 was calculated by the following method. Equipment: Shimadzu Corporation GC-14A Column: PEG20M20% Chromosorb W loaded 2m glass column (Phenomenex) Internal standard: Amyl alcohol Detector: FID detector Column temperature: 100℃ Sample concentration: 5% DMF solution The calibration curves for styrene and amyl alcohol were prepared in advance, and the content of styrene monomer in the sample was calculated based on this calibration curve, and the polymerization rate was calculated from the amount of styrene monomer remaining relative to the amount charged. In addition, the sample was dissolved in dimethylformamide (DMF) to a concentration of 5% by weight, and the supernatant liquid left to stand for 10 minutes was used as the sample solution.
[0181] [How to check the dispersion state of amorphous vinyl resin] The toner binders obtained in the examples and comparative examples were sliced into ultrathin sections with a thickness of about 100 μm, and the dispersion state of the amorphous vinyl resin (B) was stained with ruthenium tetroxide at a concentration of 1 for 3 minutes using a vacuum electron staining device (VSC1R1H, manufactured by Filgen Co., Ltd.), and the dispersion state of the amorphous vinyl resin (B), which appeared gray or black when stained with ruthenium tetroxide, was then confirmed by observing the cross section of the toner binder at a magnification of 10,000 times using a transmission electron microscope (TEM).
[0182] The physical properties of the toner binders (E-1) to (E-15) and (E'-1) to (E'-5) produced in the examples and comparative examples were measured, and the results are shown in Table 3. Table 3 also shows the type and amount of materials used in the production of each toner binder, the weight ratio of the materials, the absolute value of the difference between the SP value of the resin (A) and the SP value of the resin composition (X), and the production conditions.
[0183] [Table 3]
[0184] <Example 16: Production of toner (T-1)> To 86 parts of the toner binder (E-1) of Example 1, 7 parts of a pigment carbon black [MA-100, manufactured by Mitsubishi Chemical Corporation], 5 parts of a release agent Fischer-Tropsch wax [FT-0070, manufactured by Nippon Seiro Co., Ltd.], and 1 part of a charge control agent [T-77, manufactured by Hodogaya Chemical Co., Ltd.] were added, and a toner was prepared by the following method. First, the mixture was premixed using a Henschel mixer [FM10B, Nippon Coke & Engineering Co., Ltd.], and then mixed using a twin-screw mixer [PCM-30, Ikegai Co., Ltd.]. The mixture was then finely pulverized using a supersonic jet mill, Labojet [KJ-25, Kurimoto Iron Works Co., Ltd.], and classified using an elbow jet classifier [EJ-L-3 (LABO) type, Matsubo Co., Ltd.] to obtain toner particles with a volume average particle size (D50) of 7 μm. Next, 1 part of hydrophobic silica (Aerosil R972, manufactured by Nippon Aerosil Co., Ltd.) as a fluidizing agent was mixed with 100 parts of the toner particles in a sample mill to obtain a toner (T-1) according to Example 16.
[0185] <Examples 17 to 30 and Comparative Examples 6 to 10: Production of Toners (T-2) to (T-15) and Toners (T'-1) to (T'-5)> Except for using the materials listed in Table 4 in the amounts listed in Table 4, the same operation as in Example 16 was performed to obtain toners (T-2) to (T-15) of Examples 17 to 30 and toners (T'-1) to (T'-5) of Comparative Examples 6 to 10.
[0186] The toners (T-1) to (T-15) and (T'-1) to (T'-5) produced in Examples 16 to 30 and Comparative Examples 6 to 10 were subjected to evaluation tests according to the following evaluation methods. The results are shown in Table 4. Table 4 also shows the types and amounts of materials used in the production of each toner.
[0187] [Evaluation method] The measurement and evaluation methods for the low temperature fixing property, hot offset resistance, fixing width, wrapping property, heat resistant storage stability and image strength of the obtained toners (T-1) to (T-15) and (T'-1) to (T'-5) are described below, along with the criteria for judgment.
[0188] <Low temperature fixability> The toner obtained in each example was applied to the paper at 1.00 mg / cm 2 The powder was applied evenly so that it would be evenly distributed. The method for applying the powder to the paper surface was to use a printer without a thermal fixing unit. The paper was passed through a soft roller at a fixing speed (circumferential speed of the heating roller) of 213 mm / sec, and at a heating roller temperature range of 90 to 230°C in 5°C increments. The fixed image was then visually inspected for the presence or absence of cold offset, and the temperature at which cold offset occurs (MFT) was measured. The lower the temperature at which cold offset occurs, the better the low-temperature fixing ability is. Under these evaluation conditions, it is generally preferable that the MFT is 125° C. or less.
[0189] <Hot offset resistance> Using the same method as described above for low-temperature fixability, the toner was placed on the paper and the paper was passed through a soft roller at a fixing speed (heating roller peripheral speed) of 213 mm / sec and at a heating roller temperature range of 90 to 230° C. in 5° C. increments. Next, the fixed image was visually inspected for the presence or absence of hot offset, and the temperature at which hot offset occurred was measured. The higher the temperature at which hot offset occurs, the better the hot offset resistance. In this evaluation condition, a temperature of 180° C. or higher is preferable.
[0190] <Fixing width> The difference between the low fixing temperature and the hot offset resistance temperature was defined as the fixing width. The wider the fixing width, the better the toner is. In this evaluation condition, a temperature of 70° C. or higher is preferable.
[0191] <Winding ability> The toner obtained in each example was applied to the paper at 1.00 mg / cm 2The powder was evenly placed on the paper surface. The powder was placed on the paper surface using a printer with the heat fixing machine removed. The paper was passed through a belt fixing machine at a fixing speed (circumferential speed of the heating roller) of 320 mm / sec and a heating roller temperature range of 150 to 180°C in 10°C increments (a total of four checks). Next, the presence or absence of wrapping of the fixing paper around the belt fixing machine was visually confirmed, and if wrapping around the fixing paper was not observed, the presence or absence of wrinkles in the fixing paper was visually confirmed, and the paper was evaluated according to the following criteria. The following criteria are A, B, C, and D in order of superiority, and if the evaluation result is A or B, the wrapping is excellent.
[0192] [Evaluation Criteria] A: No wrapping is observed, and no wrinkles are observed in the fixing paper. B: No wrapping is observed, but wrinkles are observed in the fixing paper. C: Wrapping was observed once. D: Wrapping was observed more than twice.
[0193] <Heat-resistant storage stability> 1 g of the toner obtained in each example and 0.01 g of Aerosil R8200 (manufactured by Evonik Japan Co., Ltd.) were mixed in a shaker for 1 hour. The mixture obtained after mixing was placed in a sealed container and left to stand for 48 hours in an atmosphere of 40°C temperature and 80% humidity. The degree of blocking was visually judged and the heat-resistant storage stability was evaluated according to the following criteria. The following criteria are A, B, C, and D in order of superiority, and if the evaluation result is A or B, the heat-resistant storage stability is excellent.
[0194] [Evaluation Criteria] A: No blocking occurred at all (excellent heat resistance and storage stability). B: Some blocking has occurred, but the product crumbles easily when touched (excellent heat resistance and storage stability). C: Blocking has occurred in some areas, and the material does not crumble easily when touched (poor heat resistance). D: Blocking occurred throughout the film (heat resistance and storage stability were significantly poor).
[0195] <Image Intensity> The images fixed in the above-mentioned low-temperature fixing property evaluation were subjected to a scratch hardness test in accordance with JIS K5600-5-4 (1999) by applying a load of 10 g from directly above a pencil fixed at a 45-degree angle using a manual scratching method, and the image strength was evaluated from the pencil hardness at which the image was not scratched. A higher pencil hardness means better image strength. Generally, HB or higher is preferred.
[0196] [Table 4]
[0197] As is clear from the evaluation results in Table 4, all of the toners (T-1) to (T-15) according to Examples 16 to 30, which were produced by the production method of the present invention, obtained excellent results in all performance evaluations. On the other hand, the toners (T'-1) to (T'-5) according to Comparative Examples 6 to 10, which were produced by methods other than the production method of the present invention, were inferior in some performances, and none of them was excellent in all performance evaluations. [Industrial Applicability]
[0198] The toner binder obtained by the production method of the present invention is excellent in hot offset resistance, fixing width, winding property and image strength while maintaining low-temperature fixing property and heat-resistant storage stability, and can therefore be suitably used as a toner binder for developing electrostatic images used in electrophotography, electrostatic recording, electrostatic printing, etc. The toner binder obtained by the production method of the present invention is also suitable for use as an additive for paints, an additive for adhesives, particles for electronic paper, etc.
Claims
1. A step 1 of obtaining a resin composition (X) by polymerizing a monomer composition (B0) containing a monomer (b1) having a vinyl group in the presence of a crystalline vinyl resin (C); Step 2 of mixing the resin composition (X) and the amorphous polyester resin (A), A method for producing a toner binder, wherein the crystalline vinyl resin (C) is a polymer of a monomer composition (C0) containing a monomer (c1) and a monomer (c2), the monomer (c1) is a (meth)acrylate having 21 to 40 carbon atoms and a chain hydrocarbon group, and the monomer (c2) is a monomer having 6 or less carbon atoms and a vinyl group.
2. 2. The method for producing a toner binder according to claim 1, wherein the weight ratio of the monomer (c1) in the monomer composition (C0) is 40 to 90% by weight based on the total weight of the monomer composition (C0).
3. 3. The method for producing a toner binder according to claim 1, wherein the weight ratio of the crystalline vinyl resin (C) used in step 1 is 30% by weight or more based on the total weight of the crystalline vinyl resin (C) and the monomer composition (B0).
4. The method for producing a toner binder according to any one of claims 1 to 3, wherein an amorphous polyester resin (A) and a resin composition (X) satisfying the following formula (1) are used: 500 A 2017 X |≦1.1 (1) [However, SP A is the solubility parameter (cal / cm) of polyester resin (A). 3 ) 1/2 represents SP X is the solubility parameter (cal / cm) of the resin composition (X) 3 ) 1/2 represents.]
5. 5. The method for producing a toner binder according to claim 1, wherein the polymerization temperature in step 1 is 110° C. to 190° C.
6. The method for producing a toner binder according to any one of claims 1 to 5, wherein the mixing in step 2 is carried out at a temperature of 100°C to 180°C.
Citation Information
Patent Citations
Toner for electrostatic charge image development and method for producing toner
JP2011180298A
Toner for electrostatic charge image development, electrostatic charge image developer, toner cartridge, process cartridge, image forming apparatus, and image forming method
JP2013024920A
Toner
JP2014142632A
Toner binder and toner
JP2018156074A
Toner binder
JP2019207400A
